Physiological and transcriptomic analyses reveal the mechanism of improved mango storage by pre-harvest GA₃ and CPPU treatment - Tang-xin Jiang; Bi-xia Wang; Zhi-xi He; Jing-tang Zhang; Cong Luo; Xin-hua He (Postharvest Biology and Technology, 2027)

Intestinal disruption and sex-dependent gut microbial responses following benzo[a]pyrene exposure in the male-pregnant seahorse Hippocampus erectus - Lu Tang; Tong Wang; Yuanyuan Xue; Shiyi Zheng; Fang Wang; Mingzhu Li; Xiaolei Su; Hailong Chen; Qing Chu; Qiangde Liu; Cong Liu; Wuhong Lv; et al. (Marine Pollution Bulletin, 2026)

Cyclic loading test and numerical investigation on the seismic behavior of partially precast composite piers with UHPC shell - Jiahao Tang; Lifeng Li; Weimeng Jin; Ning Wang; Qizhi Zhang; Cong Zhou (Soil Dynamics and Earthquake Engineering, 2026)

Study on fuel cell performance consistency with multi-dimensional data-driven model and high-resolution current measurement - Cong Yin; Mengting Lai; Haiyu Yang; Kaixin Huang; Yuqin Luo; Hao Tang (Fuel, 2026)

Editorial Expression of Concern: Role of autophagy in early brain injury after subarachnoid hemorrhage in rats - Hongbo Zhao; Zhiyong Ji; Deji Tang; Cong Yan; Wenyang Zhao; Cheng Gao (Molecular Biology Reports, 2026)

Digital twin modelling of shield tunneling undercrossing existing tunnels: A case study - Qiujing Pan; Yiming Zhang; Cong Tang; Weibo Luo; Zihan Yang; Mingfeng Lei (Tunnelling and Underground Space Technology, 2026)

The Holocene transgression in the Bohai Sea: insights from multi-proxy sedimentary records - Lichao Tang; Ya Ping Wang; Yuanfu Yue; Wei Feng; Fu Wang; Cong-Qiang Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rapid preliminary screening of amine absorbents for post-combustion CO2 capture - Xi Tang; Bin Xu; Xiaoyi Gao; Xiaoshan Li; Ge Gao; Wen Chen; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Piezoelectric-photocatalysis assisted chemical mechanical polishing: A cost-effective and efficient approach to atomic-scale processing of RS-SiC surfaces - Xingwang Xu; Jiayi Liu; Bin Lin; Tianyi Sui; Jinming Li; Bingrui Lv; Pengcheng Zhao; Hetian Hou; Cong Chen; Hualong Zhang; Yuhao Zhang; Jinhua Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Efficient electrocatalytic reduction of nitrate to ammonia over oxygen vacancy-rich copper - Shixuan Zhan; Cong Yan; Yang Tang; Yuanhao Wang; Xiao Jin Yang; Hanjun Hu (Journal of Environmental Chemical Engineering, 2026)

Erosion rates in the northern coast of Southern China Sea: Insights from granitic cosmogenic nuclide depth profiles - Hao Liang; Ying Xu; Ziye Zhou; Zhen Chen; Yongjie Tang; Cong Chen; Ke Zhang; Ping Huang; Zhigang Li; Gege Hui; Yipeng Zhang; Qingying Tian; et al. (Geomorphology, 2026)

Window-specific effects of ultraviolet radiation and air pollution on ovarian reserve in infertile women: A retrospective cohort study - Qi Tang; Cong Fu; Hongyu Du; Qing Liu; Kui Yang; Zhuoni Xiao; Yanqing Xu (Environmental Pollution, 2026)

Lateral dynamic response of a vertical pile under ice impact: linking ice fragmentation, pile-soil interaction and displacement demand - Wenqiang Xing; Ke Wang; Shengyi Cong; Shanzhen Li; Liang Tang; Xianzhang Ling (Ocean Engineering, 2026)

Multi-objective evaluation of CO2-ECBM operating conditions in deep low-permeability coal reservoirs: Trade-offs among CH4 recovery, CO2 storage, and permeability preservation - Qian Zhang; Cong Wang; Pingsong Zhang; Yang Li; Caifang Wu; Huihu Liu; Shuheng Tang (Journal of Cleaner Production, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

Energy-efficient modulation of CO2 phase-change absorbents using tertiary amines: A comprehensive analysis combining experimental and mechanistic approaches - Ge Gao; Wenying Dong; Xuehao Li; Yansen Hu; Xiaoshan Li; Xi Tang; Wen Chen; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2026)

Selective confinement of KOH within activated carbon cloth: A strategy for fast, low-temperature regenerable direct air capture - Kai Tang; Haoqian Chen; Yuxiang Wu; Xiaoshan Li; Cong Luo; Liqi Zhang; Fan Wu (Chemical Engineering Journal, 2026)

Revisiting the formation and differentiation of Neoproterozoic continental arc crust in the western Yangtze Block, South China - Yu Zhu; Xiao-ping Xia; Feng Guo; Yan-jie Tang; Xin Zhu; Chang-xin Yin; M.P. Manu Prasanth; Ren-zhi Zhu; Min Liu; Zhuang Guo; Jiang-feng Qin; Fang-yi Zhang; et al. (Chemical Geology, 2026)

Trace element composition of cold-water corals from coastal Antarctic surface sediments: Implications for biomineralization mechanisms and paleoceanographic reconstructions - Derong Zhao; Sang Chen; Junru Guan; Haihong Wu; Xin Chen; Cong Zeng; Zhekai Tang; Maojun Yan; Ning Zhao; Liqiang Xu; Meng Zhou (Chemical Geology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

A multi-scale fusion approach for gpr data interpretation: integrating instantaneous attributes and CNN for efficient subsurface void detection - Wenqiang Ding; Changying Ma; Cong Zhou; Wenwu Tang; Lei Gao; Mengxue Dai (Journal of Applied Geophysics, 2026)

Construction of bioaffinity antibacterial coatings via piezoelectric effect-enhanced alkaline microenvironment - Zhe Hao; Cong Wu; Ning Zhao; Ran Liu; Guolu Mu; Yufei Tang (Chemical Engineering Journal, 2026)

Synergistic aggregation inhibition and radical-catalyzed doping in 3D crosslinked electron transport layer for efficient and stable inverted perovskite solar cells - Daizhe Wang; Guibin Shen; Dongqing He; Cong Kang; Chaofeng Zhu; Baitong Yan; Jiadong Xue; Xueye Ren; Xiaochen Sun; Dongyan Tang; Yong Zhang; Zhipeng Kan; et al. (Chemical Engineering Journal, 2026)

The biofilm detachment modes and mechanisms in porous media - Haomin Yang; Yangyang Tang; Zheng Zhang; Jiankun Wang; Cong Tao; Xiaoling Wang (Biodegradation, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

miR395m/n negatively regulate resistance to Colletotrichum gloeosporioides in Malus domestica - Baodong Zhang; Jinqi Tang; Jialin Cong; Qiulei Zhang; Zongshan Zhou (Plant Science, 2026)

From tomato peel waste to functional magnetic biochar: Recyclable adsorbent for efficient phenol removal from wastewater - Xiulin Feng; Xuedi Zhan; Xuening Sun; Yue Zhang; Jiangfen Duan; Cong He; Haifeng Zhang; Yakun Tang; Jinhui Yang (Journal of Water Process Engineering, 2026)

Study on the microscopic failure mechanisms of snow under mixed loading conditions based on FDM-DEM - Chenyu Li; Chong Shi; Jie liu; Cong Zhang; Xuan Tang; Aifeima Ahetamuxi (Cold Regions Science and Technology, 2026)

A coupled macro–micro prediction model for desiccation shrinkage deformation of freeze–thawed expansive soils incorporating the pore size-volume dual microstructure parameters - Shengyi Cong; Xinyu Li; Liang Tang; Xianzhang Ling; Ze Li; Sai K. Vanapalli (Transportation Geotechnics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Revealing the roles of biochar in anaerobic digestion of waste activated sludge with the overloading accumulation of humic acids - Wen-Tao Li; Fei Wang; Qing-Bin Meng; Sheng-Jie Sun; Cong-Cong Tang; Lei Yang; Jun Lan; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhang-Wei He (Journal of Water Process Engineering, 2026)

NaOH regulation of steel slag carbonation: Interfacial activation and kinetic enhancement - Wenjing Tang; Jiale Tian; XinYu Zhu; Yu Cong Ge; Tao Wang; Zhenwei Yi; Mengxiang Fang; Kun Luo; Xiang Gao (Journal of Environmental Chemical Engineering, 2026)

Supercritical CO2 adsorption behavior in deep coal seams of the Qinshui Basin: Model, Mechanisms, and implications for geological storage - Cong Wang; Qian Zhang; Shuheng Tang; Caifang Wu (Fuel, 2026)

Smart autologous plasma-ICG self-assembled carriers prolong half-life of growth factors and enhance antibacterial effect for periodontitis therapy - Hailun Zhou; Jun Zhou; Xiaoqi Wang; Li Tang; Cong Liu; Chunyun Liang; Hejia Qin; Shufang Zhuo; Ao Long; Fengyuan Zhou; Lu Liu; Wenjin Chen; et al. (Chemical Engineering Journal, 2026)

Vegetation and human-activity signals from pollen over the last millennium: Implications for organic carbon sources in the Pearl River estuary - Shaohua Yu; Fang Chen; Qing Zhu; Kangyou Huang; Yang Zhou; Cong Wu; Chang Zhuang; Xia Jing; Kaijun Cao; Dehao Tang (CATENA, 2026)

Rapid and sensitive detection of feline herpesvirus-1 using fluorescent microspheres as labels for immunochromatographic test strips - Peipei Shao; Yuexiao Lian; Xiangnan Liu; Huizhen Liu; Jiantao Yu; Yongping Tang; Feng Cong; Ye Ge (Veterinary Research Communications, 2026)

Root morphological strategies enhance growth of Cunninghamia lanceolata and Schima superba under nitrogen stress in intercropping systems - Xiao-Li Yan; Cong Cheng; Yunhao Xu; Jiaxiang Yu; Zhaozhao Wang; Yanru Wang; Xinghao Tang; Pengfei Wu; Xiangqing Ma; Lu-Ping Qu (Plant and Soil, 2026)

Two phases of early Palaeozoic magmatism at the Wude area in the western Bainaimiao arc (Inner Mongolia, China): Petrogenesis and tectonic implications - Cong Ding; Zhicheng Zhang; Yunxi Meng; Jianzhou Tang; Qi Wang; Huaihui Zhang; Baofu Han (Acta Geochimica, 2026)

Emerging Viruses in Decapod Crustaceans: A Global Review - Xuan Dong; Guohao Wang; Kejun Wang; Kaisong Zhang; Hua Xu; Liying Wang; Xuan Li; Liang Qiu; Win Surachetpong; Jing Wang; Jee Eun Han; Kathy F. J. Tang; et al. (Reviews in Aquaculture, 2026)
Due to its advantages of a short production cycle, wide market demand, and profitability, decapod crustacean aquaculture has become one of the fastest‐growing food production systems. However, disease outbreaks have become one of the most important factors limiting the sustainability of decapod crustaceans. This review synthesizes current advancements in the understanding of emerging viral pathogens in decapod crustacean aquaculture, with emphasis on their genomic‐based taxonomical classification, susceptible hosts, global distribution, clinical manifestations, pathogenic mechanisms, diagnostic developments, and management strategies. This paper summarizes details of emerging viruses with confirmed pathogenicity (such as decapod iridescent virus 1), as well as viruses with uncertain or yet‐unconfirmed pathogenic roles. In addition, we highlight the role of next‐generation sequencing in virus discovery and examine the challenges posed by coinfection with other microorganisms. This review provides information to help the decapod crustacean aquaculture industry in setting up early warning systems to prevent the introduction of emerging pathogens into the production systems.

New cutting tool wear testing method for evaluating the influence of foam additive on plowing effect during shield TBM tunnelling in dense sandy gravel ground - Shao-Hui Tang; Xiao-Ping Zhang; Quan-Sheng Liu; Yu-Cong Pan; Wei-Qiang Xie; Xin-Fang Li; Hao-Jie Wang (Tunnelling and Underground Space Technology, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Biogeochemical cycling of carbon and nitrogen in terrestrial-aquatic interfaces: Mechanisms, driving factors, and eco-environmental significance - Wei Guo; Weiping Tang; Liyuan Sang; Xu Zhang; Wenhong Wang; Anji Li; Yunchao Lang; Xinchu Wang; Hu Ding; Guang-Hui Yu; Cong-Qiang Liu (Science China Earth Sciences, 2026)

Genetic mapping and identification of a major quantitative trait locus associated with the high fiber strength introgressed from Gossypium barbadense - Kai Wang; Haohong Tang; Cong Sun; Xiaohu Ma; Shen Ren; Jie Li; Xinyu Zhang; Shuaishuai Cheng; Xianpeng Xiong; Jie Sun (Plant Cell Reports, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Methane production enhancement from anaerobic digestion of waste activated sludge with corn straw-derived biochar: Insights into the roles of tubular and lamellar structures - Shi-Yu Gao; Wen Hu; Lijuan Gao; Cong-Cong Tang; Xiao-Yan Chen; Ai-Juan Zhou; Wentao Li; Wenzong Liu; Zhang-Wei He (Journal of Water Process Engineering, 2026)

Bioactive carbon dots as antibacterial neural interface for neuron recording - Wanyu Tang; Yang Wang; Huan Wang; Zhaoliang Ni; Xinyu Sun; Liu Cong; Xiaoyi Zuo; Ziying Meng; Shaofang Zhang; Hao Wang; Jinsong Ren; Shuangjie Liu; et al. (Chemical Engineering Journal, 2026)

Erratum to: Ononin inhibits triple-negative breast cancer lung metastasis by targeting the EGFR-mediated PI3K/Akt/mTOR pathway - Kumar Ganesan; Cong Xu; Jianming Wu; Bing Du; Qingqing Liu; Yue Sui; Cailu Song; Jinhui Zhang; Hailin Tang; Jianping Chen (Science China Life Sciences, 2026)

Nicotinamide prevents anti-PD1 immune checkpoint inhibitor-associated early stages of cardiotoxicity - Lu Bai; Jing Zhao; Kang Dong; Maomao Zhao; Yanhang Zhao; Qianyue Cong; Yongxiang Wang; Xiaowei Niu; Jianming Tang; Ming Bai (Science China Life Sciences, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Influence mechanisms of mesoscopic mechanical properties in granite using the Grain Seed Growth Model - Wei Qiao; Chong Shi; Liang Liu; Cong Zhang; Xuan Tang; Qianyi Yang (Computers and Geotechnics, 2026)

Prediction of enhanced creep landslide displacement by analyzing multi-time-scale displacement impact factors using convolutional neural network (CNN) - Zhongdi Rong; Shengyi Cong; Liang Tang; Pengfei Chen; Yonghui Wang; Meihong Ma; Željko Arbanas (Landslides, 2026)

The combined effects of drought and defoliation on non-structural carbohydrates in different organs of Chinese pine - Citian Li; Yihang Zhu; Xiangmin Liang; Xinyi Guo; Changhui Peng; Tong Li; Jiayi Tang; Cong Liu; Xin Li; Xiaolu Zhou; Hanxiong Song; Zelin Liu; et al. (Journal of Plant Research, 2026)

Reinforcement-Learning-Based Adaptive PID Depth Control for Underwater Vehicles Against Buoyancy Variations - Jian Wang; Shuxue Yan; Honghao Bao; Cong Chen; Deyong Yu; Jixu Li; Xi Chen; Rui Dou; Yuangui Tang; Shuo Li (Journal of Marine Science and Engineering, 2026)
Underwater vehicles performing sampling tasks often encounter significant buoyancy variations due to payload adjustments and environmental changes, which severely challenge the stability and accuracy of controllers. To address this issue, this paper proposes a hybrid control framework that integrates Proximal Policy Optimization (PPO) with adaptive PID tuning. The framework employs PPO to dynamically adjust PID parameters online while incorporating output saturation, stepwise quantization, and dead zone filtering to ensure control safety and actuator longevity. A dual-error state representation—combining instantaneous error and its derivative—along with actuator command buffering is introduced to compensate for system lag and inertia. Comparative simulations and experimental tests demonstrate that the proposed method achieves faster convergence, lower steady-state error, and smoother control signals compared to both conventional PID and pure PPO-based control. The framework is validated through pool tests and field trials, confirming its robustness under realistic hydrodynamic disturbances. This work provides a practical and safe solution for adaptive depth control of sampling-capable AUVs operating in dynamic underwater environments.

Similarity-model experimental investigation of seismic dynamic responses and shock-absorption-layer effects of tunnels subjected to strong mainshock–aftershock sequences - Xuan Tang; Chong Shi; Cong Zhang; Wei Qiao (Soil Dynamics and Earthquake Engineering, 2026)

From agricultural waste to water treatment functional materials: Performance study of nano zero-valent iron loaded on ramie biochar for persulfate-activated carbamazepine degradation - Weiwei Yu; Lu Lv; Yang Liu; Cong Liu; Chuandong Tang; Yuanxin Liu; Xinyan Li; Dan Liu; Yan Luo; Ji Li (Journal of Environmental Chemical Engineering, 2026)

Vegetation ecosystem responses to climate-human interactions since the Late Holocene from peat record of Niangniang Mountain, western Guizhou - Yuanfu Yue; Shixiong Yang; Liuying He; Zhuo Zheng; Xiao Zhang; Cong Chen; Qiuchi Wan; Yongjie Tang; Kangyou Huang; Fang Gu (Global and Planetary Change, 2026)

Multifunctional hydrogel with rigid–flexible synergy enables high-performance flexible supercapacitors and triboelectric nanogenerators - Jiahui Tang; Xi Yang; Jiaojiao Li; Yulin Zou; Cong Chang; Dandan Gao; Jiyang Xie; Qian Zhao; Xu Zhang; Yongyun Mao (Chemical Engineering Journal, 2026)

Stablizing metal grid electrode by deep eutectic electrolyte for long-term electrochromic smart windows - Xiaolan Li; Zhiwei Chen; Jinyu Zhou; Yuchen Meng; Xueqing Tang; Kejia Zhang; Hongbin Zhao; Zhenyong Wang; Zhenzhong Yong; Laura Maggini; Davide Bonifazi; Zhigang Zhao; et al. (Chemical Engineering Journal, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

β-glucan nanotubes improve oral doxorubicin delivery for colorectal cancer by microbiota-mediated colon targeting and reduced toxicity - Ziwei Gao; Xiaoying Hou; Jun Tang; Yi Qin; Junjie Hu; Zhenpeng Qiu; Qi Wang; Cong Chang; Xinyan Chen; Zhaohua Shi; Guohua Zheng; Hongzhi Du; et al. (Carbohydrate Polymers, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Centrifuge test determination of wharf responses due to spatially and temporally varying interactions between wharf piles and liquefied soil - Zheng Zhang; Liang Tang; Shengyi Cong; Xianzhang Ling; Chouw Nawawi (Soil Dynamics and Earthquake Engineering, 2026)

An 11,000-year vegetation and climate record from a subalpine peatland in the Luoxiao Mountains, subtropical Southeast China - Xin Zhong; Caifeng Cen; Cong Chen; Aiyan Han; Yongjie Tang; Kangyou Huang (Review of Palaeobotany and Palynology, 2026)

S-HGMS coupling technology for sustainable activated silica as a sustainable alternative: A comparative life cycle assessment - Cong Li; Xue Yang; Peihan Chen; Xuebao Tang; Xingyu Liu; Suqin Li (Process Safety and Environmental Protection, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Hierarchical porous aerogel constructed from in-situ assembled zein nanoparticles for sustainable radioactive iodine capture - Qing Shen; Cong Tang; Xiaoping Bai; Yujie Wen; Shijun Shao; Ting Huo; Shuqing Dong (Environmental Research, 2026)

CuO2-loaded quaternized chitosan-based composite nanofiber membranes: Immediate contact antibacterial for high-risk public surface engineering - Caiyun Chen; Yufei Tang; Cong Wu; Yani Sun; Bo Zhang; Kang Zhao; Zixiang Wu (Chemical Engineering Journal, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

ZnCl2-enhanced soy sauce residue biochar via single-step pyrolysis: Dual enhancement of thermal process safety and 4-chlorophenol adsorption capacity - Chongbin Zhang; Cong Wang; Jian Yang; Hongyang Li; Yongzheng Shang; Mengnan Shen; Chen Lyu; Chenyang Li; Shuang Zhong; Lulu Tang (Process Safety and Environmental Protection, 2025)

The topographic features and sedimentary environment potentially influenced the vegetation reconstruction in southwestern China since the MIS3 - Xiao Zhang; Yuanfu Yue; Ziyan Zhang; Liuying He; Xinmeng Yuan; Xintian Yu; Qiuchi Wan; Cong Chen; Yongjie Tang; Zhuo Zheng; Kangyou Huang (Quaternary Science Reviews, 2025)

The impacts of global change on the self-thinning lines for six timber species in Canada - Yanni Pu; Cong Tang; Yujie Xiao; Sida Lai; Tong Jiang; Weifan Li; Pembegul Nozohourmehrabad; Kun Xu (Forest Ecology and Management, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Aqua regia, as a carbon modifier, improves the physical properties and chemical adsorption capacities of activated carbon from passion fruit peel - Bo Jie Chen; Cong Xia; Jie Tang; Xinhong Dong; Jing Li; Xia Li; Biyu Peng; Hock Eng Khoo (Biocatalysis and Agricultural Biotechnology, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

Co-application of porous biochar and Fe2O3 in cattle manure and wheat straw composting: mechanistic insights into greenhouse gas mitigation and nitrogen transformation - Xu Yang; Cong Shao; Xuan Wu; Wenxin Zhang; Kuok Ho Daniel Tang; Xiu Zhang; Junting Pan; Ronghua Li (Journal of Environmental Management, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Metal exposure and internalizing and externalizing psychobehavioral problems in a Chinese early adolescent cohort - Ting Tang; Min Li; Mengyuan Yuan; Yonghan Li; Cong Wang; Qi Zhong; Xueying Zhang; Yichao Huang; Fangbiao Tao; Puyu Su; Gengfu Wang (Environmental Research, 2025)

Experimental investigation and numerical study on the seismic behavior of precast concrete piers with UHPC connection - Jiahao Tang; Lifeng Li; Meng Ye; Weimeng Jin; Xiwei Wang; Jiahao Mao; Cong Zhou (Engineering Structures, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

Preparation, characterization, fermentation properties of pectin with specific structures, and the analysis of microbial enzymes and genes involved in their degradation - Weichao Cao; Yaxian Liu; Nuo Chen; Yuhang Wang; Yiasmin Mst Nushrat; Shouzheng Qiao; Lisha Tang; Zhen Sun; Rongrong Lu; Cong Liu; Xiao Hua (Carbohydrate Polymers, 2025)

Transcriptional and post-translational regulation of wheat TaWRKY40 orchestrates ROS-mediated plant resistance against stripe rust - Jiani He; Qiongqiong Li; Chenchen Liang; Ning Wang; Jianfeng Wang; Cong Jiang; Zhensheng Kang; Chunlei Tang; Xiaojie Wang (Molecular Plant, 2025)

Corrigendum to “Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection” [J. Environ. Chem. Eng. 13 (5) (2025) 118803] - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yongwoo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

Microwave ultra-narrow band antenna sensor based on TiO2/MXene for room-temperature acetone detection - Jie Wei; En-Kang Wu; Ji-Hao Zhang; Zhen Zhang; Xiao-Cong Tang; Tian Qiang; Yong-Woo Jang; Xiao-Feng Gu; Meng Zhao; Svetlana von Gratowski; Jun-Ge Liang; Ming-Yang Yan; et al. (Journal of Environmental Chemical Engineering, 2025)

The potential of nanoscale zero-valent iron as an additive for swine slurry and pulverized wolfberry branch co-composting from the perspective of nitrogen retention and greenhouse gas emissions - Xu Yang; Miaoqu Wang; Cong Shao; Yang Wang; Kuok Ho Daniel Tang; Bowen Wang; Hua Li; Ronghua Li; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Biochar-activated peracetic acid for the degradation of emerging contaminants - Shi-Yu Gao; Cong-Cong Tang; Ai-Juan Zhou; Zhaobo Chen; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Zhang-Wei He (Journal of Environmental Chemical Engineering, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Revisiting the role of solution aggregation in CO₂ desorption: Insights of mass transfer and energy consumption in phase-change absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Chemical Engineering Journal, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

A photoelectrochemistry-based “on-off-on” strategy to study the transformation reaction of hydroxyl radicals in Fenton-like advanced oxidation process - Cong Tang; Xiaoping Bai; Qing Shen; Yujie Wen; Shijun Shao; Gaosen Zhang; Shuqing Dong (Journal of Water Process Engineering, 2025)

High-efficient and superfast capture of Hg2+ , Pb2+, and Ag+ ions from wastewater using ethylenediamine intercalated MoSe2 nanoflowers - Kaini Zhu; Zhufeng Qin; Yusheng Bao; Cong Tang; Jingjing Jiang; Sikai Qin; Xing-Can Shen; Changping Ruan (Journal of Hazardous Materials, 2025)

Effect of humic acid on the transport of vanadium oxides nanoparticles in water saturated packed columns - Cong Tan; Baogang Zhang; Wei Zhang; Yang Tang; Xinzhao Luo (Journal of Hazardous Materials, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Dual-channel emission probe for monitoring biothiols and H2S in various scenarios: Living cells, plants, and food - Yujie Wen; Xiaomeng Xu; Cong Tang; Shuqing Dong; Yaya Wang; Yue Hu; Shijun Shao (Journal of Hazardous Materials, 2025)

Novel mass transfer kinetics model for predicting phase separation behavior in CO2 capture with energy-saving biphasic absorbents - Bin Xu; Xiaoyi Gao; Wufeng Jiang; Xi Tang; Xiaoshan Li; Cong Luo; Fan Wu; Liqi Zhang (Journal of Cleaner Production, 2025)

Effect of pulsation frequencies on the fracture characteristics of CO2 foam fractured coal: An experimental study - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Hexiang Xu; Xinyu Zhu; Shuxun Sang; Meng Wang; Shiqi Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; et al. (Gas Science and Engineering, 2025)

Multimetallic intra-nanogap nanozyme-mediated lateral flow immunoassay for ultrasensitive and multimode detection of K. pneumonia in clinical samples - Weixia Zhi; Xinjie Guo; Yichu Nie; Lu Nie; Tingting He; Li Dai; Jing Xu; Xiangxin Zong; Jun Xu; Huaihong Cai; Yong Tang; Yanguang Cong; et al. (Chemical Engineering Journal, 2025)

Phase separation prediction modeling and structure-activity relationship of CO2 capture by biphasic amine absorbents based on phase separation load - Xiaoyi Gao; Bin Xu; Wufeng Jiang; Xi Tang; Muyi Li; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

Deciphering the synergistic effects and mechanisms of biochar and magnetite contained in magnetic biochar for enhancing methane production in anaerobic digestion of waste activated sludge - Hong-Yu Jin; Yong-Xiang Ren; Cong-Cong Tang; Shuai Zhang; Jiabin Wang; Ai-Juan Zhou; Bin Liang; Wenzong Liu; Aijie Wang; Zhang-Wei He (Water Research, 2025)

Settlement-based triple factor framework for long-term safety assessment of immersed tunnel - Shu-Yu He; Cong Tang; Mi Pan; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2025)

Prediction of airborne bacterial concentrations and identification of critical factors in contaminated waste facilities: Insights into interpretable machine learning models - Yanyan Guo; Youcai Zhao; Guofang Zhang; Ji Tang; Cong Ma; Xu Xing; Tao Zhou (Journal of Hazardous Materials, 2025)

TdCCA with Dual-Modal Signal Fusion: Degenerated Occipital and Frontal Connectivity of Adult Moyamoya Disease for Early Identification - Yuchen Ran; Yingwei Fan; Shuang Wu; Chao Chen; Yangxi Li; Tianxin Gao; Houdi Zhang; Cong Han; Xiaoying Tang (Translational Stroke Research, 2025)

Colorful transmissive all-solid-state electrochromic devices empowered by optical resonant cavities - Taoyang Zhang; Yongjie Dai; Yaowu Li; Xueqing Tang; Yuxin Hu; Zhijie Chen; Shengbin Wu; Huidong Li; Qinggeng Lin; Shan Cong; Zhigang Zhao (Chemical Engineering Journal, 2025)

Triple-effect strategy with taxifolin-whitlockite nanoparticles embedded hydrogel for osteoporotic bone defect repair and bone homeostasis modulation - Jiawei Jiang; Cong Cai; Song Li; Yuan Xiong; Changyu Liu; Zixing Shu; Jingxi Yang; Meng Zheng; Tingxuan Tang; Wenbin Liu; Hao Zhu; Mohammad-Ali Shahbazi; et al. (Chemical Engineering Journal, 2025)

Paleoenvironmental changes and nitrogen cycling of the lacustrine systems following the Toarcian Oceanic Anoxic Event in the Sichuan Basin (China): Insights from nitrogen isotopes - Yang Bai; Jianfa Chen; Jin Wu; Wenzhe Gang; Václav Suchý; Cong Chen; Xuemin Xu; Rao Fu; Jiaqi Zhang; Shuaiqi Tang (Chemical Geology, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

Efficient hydrogen conversion of toluene via biochar-supported Fe-Cu bimetallic catalyst under CO2-steam synergistic conditions - Jiankai Zhang; Xinjia Wang; Hui Jin; Jinzheng Wang; Haofeng Yang; Cong Dong; Guoneng Li; Yuanjun Tang; Haolin Liu; Chao Ye (Journal of Environmental Chemical Engineering, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

On-site identification of black soil thickness based on drill-core imaging and deep learning - Lei Qiao; Jiabao Zhang; Xicai Pan; Rutian Bi; Jienan Xu; Cong Tang; Kwok Pan Chun (CATENA, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Migration of vanadium oxide nanoparticles in saturated porous media - Wei Zhang; Baogang Zhang; Xinzhao Luo; Cong Tan; Yang Tang; Yiyun Yang (Journal of Hazardous Materials, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

A novel index for mapping crop residue covered cropland using remote sensing data - Wenqian Zhang; Wenjuan Li; Cong Wang; Qiangyi Yu; Huajun Tang; Wenbin Wu (Computers and Electronics in Agriculture, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Few-layer molybdenite-derived MoS2 nanosheets and SnO2 nanostructures heterojunctions for high-performance NH3 detection: Insights from experimental and DFT analysis - Jinzhou Bai; Chao Tang; Sikai Zhao; Siyao Liu; Wenxin Wang; Cong Han; Qiang Zhao; Yanbai Shen (Chemical Engineering Journal, 2025)

Towards digitalized maintenance of operating tunnels: A text documents-based defect evaluation and visualization - Xuefeng Ou; Cong Tang; Tongming Qu; Shiquan Xu; Ye Zhou; Jiao Tian (Tunnelling and Underground Space Technology, 2025)

A flexible framework for built-up height mapping using ICESat-2 photons and multisource satellite observations - Xiayu Tang; Guojiang Yu; Xuecao Li; Hannes Taubenböck; Guohua Hu; Yuyu Zhou; Cong Peng; Donglie Liu; Jianxi Huang; Xiaoping Liu; Peng Gong (Remote Sensing of Environment, 2025)

The structure–activity relationship for CO2 absorption heat of chain diamines: Effects of amino types, methyl/ethyl groups, and chain lengths - Xi Tang; Ge Gao; Wufeng Jiang; Bin Xu; Fan Wu; Cong Luo; Xiaoshan Li; Liqi Zhang (Chemical Engineering Journal, 2025)

The Influences of Mineral Components and Pore Structure on Hydraulic Fracture Propagation in Shale - Tianjiao Li; Mingyu Yao; Yingjie Xia; Xianhui Feng; Wenyu Cong; Yaoli Shi; Chun’an Tang (Rock Mechanics and Rock Engineering, 2025)

Spatio-temporal scales of the Chinese Daqu microbiome: Heterogeneity, niche differentiation, and assembly mechanisms - Jie Tang; Junlin Wei; Yong Yang; Xiangyang Ge; Qiancheng Zuo; Cong Zhao; Yongguang Huang (Trends in Food Science & Technology, 2025)

A novel strategy for the efficient purification of quartz ore: Experiments, DFT calculations, and life cycle assessment - Cong Li; Xuebao Tang; Xingyu Liu; Suqin Li (Process Safety and Environmental Protection, 2025)

[C3N3S3]3– intercalated Mg/Al layered double hydroxide for high-efficiency and superfast removal of Pb2+, Hg2+, and separation of Ag+ ions: Performance and mechanism - Zhuoyan Li; Kaini Zhu; Houjuan Hu; Ying Wang; Jingjing Jiang; Cong Tang; Xing-Can Shen; Changping Ruan (Journal of Environmental Chemical Engineering, 2025)

Genomic determinants of biological age estimated by deep learning applied to retinal images - Yu Huang; Mohammad Ghouse Syed; Ruiye Chen; Cong Li; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Shulin Tang; Jing Liu; Shunming Liu; Sundar Srinivasan; et al. (GeroScience, 2025)
With the development of deep learning (DL) techniques, there has been a successful application of this approach to determine biological age from latent information contained in retinal images. Retinal age gap (RAG) defined as the difference between chronological age and predicted retinal age has been established previously to predict the age-related disease. In this study, we performed discovery genome-wide association analysis (GWAS) on the RAG using the 31,271 UK Biobank participants and replicated our findings in 8034 GoDARTS participants. The genetic correlation between RAGs predicted from the two cohorts was 0.67 ( P = 0.021). After meta-analysis, we found 13 RAG loci which might be related to retinal vessel density and other aging processes. The SNP-wide heritability ( h 2 ) of RAG was 0.15. Meanwhile, by performing Mendelian randomization analysis, we found that glycated hemoglobin, inflammation hemocytes, and anemia might be associated with accelerated retinal aging. Our study explored the biological implications and molecular-level mechanism of RAG, which might enable causal inference of the aging process as well as provide potential pharmaceutical intervention targets for further treatment. Graphical Abstract

New quantified climate reconstruction in southern China suggests a potential influence of winter cloud cover across East Asia during the Holocene - Xiao Zhang; Cong Chen; Kexin Wang; Meihuan Li; Yuanfu Yue; Jun Cheng; Mengna Liao; Kai Li; Lina Liu; Zhanghua Wang; Rachid Cheddadi; Qiuchi Wan; et al. (Science of The Total Environment, 2025)

Insights to the roles of nitrogen-doped biochar in anaerobic digestion - Zhang-Wei He; Sheng-Jie Sun; Ai-Hua Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhi-Hua Li; Ai-Jie Wang; Wen-Zong Liu (Process Safety and Environmental Protection, 2025)

Multi-perspective kinetic analysis of plastic blends under thermogravimetric pyrolysis conditions - Menghua Song; Yuanjun Tang; Jun Dong; Guoneng Li; Zhaozhi Zhou; Chao Ye; Yangqing Hu; Cong Dong; Youqu Zheng (Journal of Environmental Management, 2025)

Textured vegetable protein as a partial replacement for lean meat in salami analogues: Perspectives on physicochemical properties, flavour and proteome changes - Ying Li; Xin Liu; Jian Zhang; Zijiang Yang; Cong Zhou; Peng Wu; Chunbao Li; Xinglian Xu; Changbo Tang; Guanghong Zhou; Yuan Liu (Food Chemistry, 2025)

Surfactant-modified zein nanoparticles adsorbents for ultrafast and efficient removal of Cr(VI) - Qing Shen; Xiaomeng Xu; Xiaojing Liang; Cong Tang; Xiaoping Bai; Shijun Shao; Qing Liang; Shuqing Dong (Environmental Research, 2025)

Hyaluronanized gold nanoparticles functionalized with CTX-II antibody for early diagnosis and treatment of knee osteoarthritis - Cheng Chen; Cong Tang; Kaiquan Chen; Muhai Deng; Xiangling Pu; Tao Hu; Zhiyu Chen; Ling Zhong; Yunsheng Jiang; Yang Huang (Chemical Engineering Journal, 2025)

Ternary organic solar cells containing fused-benzotriazole polymer as donor and two types of benzotriazole molecules as guest component - Ning Sun; Leyi Tang; Lei Yang; Mengzhen Du; Zongtao Wang; Qing Guo; Peiqing Cong; Yanfang Geng; Jimin Du; Erjun Zhou (Chemical Engineering Journal, 2025)

A transformed Prussian blue analog as host of I2 for long-life aqueous zinc-iodine battery - Yang Qian; Ge Chang; Cong Huang; Yujie Yang; Yisu Hao; Qunli Tang; Aiping Hu; Yanhua Li; Xiaohua Chen (Chemical Engineering Journal, 2025)

Enhanced aerobic denitrifiers in wastewater treatment: Optimization of aeration mode and mechanistic study - Cong Chen; Yuhan Zhu; Jun Li; Peng Tang; Peng Gao; Xin Zhang; Andong Zhao (Journal of Water Process Engineering, 2024)

Relationship between root characteristics and saturated hydraulic conductivity in a grassed clayey soil - Ling-Xin Cui; Qing Cheng; Pui San So; Chao-Sheng Tang; Ben-Gang Tian; Cong-Ying Li (Journal of Hydrology, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Insight into the responses of the anammox granular sludge system to tetramethylammonium hydroxide (TMAH) during chip wastewater treatment - Andong Zhao; Jun Li; Peng Gao; Peng Tang; Tingting Liu; Xin Zhang; Xuming Liu; Cong Chen; Zehao Zhang; Zhaoming Zheng (Environmental Research, 2024)

Macrophage activation syndrome in Sepsis: from pathogenesis to clinical management - Shunyao Chen; Cong Zhang; Jialiu Luo; Zhiqiang Lin; Teding Chang; Liming Dong; Deng Chen; Zhao-Hui Tang (Inflammation Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

The normalized difference yellow vegetation index (NDYVI): A new index for crop identification by using GaoFen-6 WFV data - Yanbing Wei; Miao Lu; Qiangyi Yu; Wenjuan Li; Cong Wang; Huajun Tang; Wenbin Wu (Computers and Electronics in Agriculture, 2024)

Distinguishing contributions of diverse sediment components to vanadium transport, immobilization and transformation in aquifer - Jinxi He; Baogang Zhang; Cong Tan; Yang Tang; Zhongjun Shen; Songlin Wu; Shungui Zhou (Water Research, 2024)

Long-term Holocene warming trend in Southern China revealed by corrected pollen data - Qiuchi Wan; Cong Chen; Kunshan Bao; Xiao Zhang; Yongjie Tang; Xin Zhong; Zhuo Zheng; Kangyou Huang (Quaternary Science Reviews, 2024)

Geochronology, petrogenesis and tectonic implications of rodingites from the Baixingtu ophiolite in central Inner Mongolia, southeastern Central Asian Orogenic Belt - Cong Ding; Zhicheng Zhang; Qi Wang; Jianzhou Tang (Journal of Asian Earth Sciences, 2024)

New insights into the functional group influence on CO2 absorption heat and CO2 equilibrium solubility by piperazine derivatives - Xi Tang; Bin Xu; Wufeng Jiang; Xiaoshan Li; Ge Gao; Fan Wu; Cong Luo; Liqi Zhang (Chemical Engineering Journal, 2024)

Roles and fates of antibiotics in anaerobic digestion of waste activated sludge: Insights to pro- and re-duction of antibiotic resistance genes - Qing-Bin Meng; Zhang-Wei He; Wenjing Yang; Wen-Tao Li; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Bacterial outer membrane vesicles-clothed nanoparticles delivered by live macrophages for potentiating antitumor photoimmunotherapy - Cong Fu; Lu Tang; Yuqi Cao; Yue Yin; Hening Liu; Jingwen Feng; Jifan Gao; Jing Li; Wei Wang (Chemical Engineering Journal, 2024)

Patterned Laser-Induced graphene enabling a High-Performance gas sensing Split-Ring resonator - Kishor Kumar Adhikari; Luqman Ali; Jie Wei; Yang Yi; Xiaocong Tang; Zheyi Li; Ju Gao; Liangzhong Mei; Yishun Qu; Junli Yin; Cong Wang (Chemical Engineering Journal, 2024)

A microfluidic analyzer based on liquid waveguide capillary cells for the high-sensitivity determination of phosphate in seawater and its applications - Jincheng Zhao; Zeming Yang; Dejing Tang; Min Qin; Wen Zhou; Cong Liu; Zhantang Xu; Yuanyue Cheng; Xianqing Zhang; Cai Li (Analytica Chimica Acta, 2024)

Hematite tailings to high-purity silica: Mechanistic studies and life cycle assessment analysis - Cong Li; Xuebao Tang; Xingyu Liu; Suqin Li (Chemosphere, 2024)

Multi-output prediction for TBM operation parameters based on stacking ensemble algorithm - Yu Tang; Junsheng Yang; Yuyang You; Jinyang Fu; Xiangcou Zheng; Cong Zhang (Tunnelling and Underground Space Technology, 2024)

Soil moisture alters the responses of alpine ecosystem productivity to environmental factors, especially VPD, on the Qinghai-Tibetan Plateau - Tao Zhang; Baoxin Shan; Mingjie Xu; Guang Zhao; Zhoutao Zheng; Yuanyuan Tang; Ning Chen; Juntao Zhu; Nan Cong; Ben Niu; Yangjian Zhang (Science of The Total Environment, 2024)

Grazing affects ecosystem traits by regulating plateau pika activities at the landscape scale - Ze Tang; Yangjian Zhang; Zhoutao Zheng; Nan Cong; Yixuan Zhu; Yao Chen; Jie Gao; Wenquan Zhu (Science of The Total Environment, 2024)

Reconstructed source method for underwater noise prediction of a stiffened cylindrical shell - Fuzhen Pang; Yang Tang; Chenhao Li; Fuchang Zhou; Cong Gao; Haichao Li (Ocean Engineering, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Microbial consortia-driven bioweathering provides new potential for sustainable recovery of rare earth elements (REE) in fly ash: From metagenome exploration to performance verification - Zhendong Yang; Cong Peng; Mikolaj Iwan; Liudong Chen; Miao He; Zhenyu Zhang; Yijing Chen; Jiayi Tang; Jing Wang; Yonghong Liu; Lukasz Drewniak; Li Zeng (Journal of Environmental Chemical Engineering, 2024)

Biochar alleviates inhibition effects of humic acid on anaerobic digestion: Insights to performances and mechanisms - Sheng-Jie Sun; Fei Wang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhihua Li; Wenzong Liu (Environmental Research, 2024)

Experimental investigation on the horizontal impact response of precast RC bridge piers with grouted sleeve connections considering defects - An He; Dun-Cong Zheng; Jian Cai; Qing-Jun Chen; Xu-Lin Tang; Jia-Bin Ye (Engineering Structures, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Fluorine substitution for aggregation transformation and exciton dissociation acceleration in non-fused electron acceptors - Leyi Tang; Hai Jiang; Peiqing Cong; Zongtao Wang; Yanfang Geng; Qing Guo; Erjun Zhou (Chemical Engineering Journal, 2024)

Micro/nano system-mediated local treatment in conjunction with immune checkpoint inhibitor against advanced-Stage malignant melanoma - Lu Tang; Hening Liu; Yue Yin; Ting Pan; Cong Fu; Yuqi Cao; Yijun Mei; Qiaqia Xiao; Ziwei Yan; Yi Yao; Haijuan Dong; Wei Wang (Chemical Engineering Journal, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Unlocking soil revival: the role of sulfate-reducing bacteria in mitigating heavy metal contamination - Cheng Hu; Zhendong Yang; Yijing Chen; Jiayi Tang; Li Zeng; Cong peng; Liudong Chen; Jing Wang (Environmental Geochemistry and Health, 2024)

Applications of multi-omics techniques to unravel the fermentation process and the flavor formation mechanism in fermented foods - Linfeng Wen; Lixin Yang; Cong Chen; Jun Li; Jiangyan Fu; Guo Liu; Qixin Kan; Chi-Tang Ho; Qingrong Huang; Yaqi Lan; Yong Cao (Critical Reviews in Food Science and Nutrition, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Antiviral C-geranylated flavonoids from Artocarpus communis - Rui-Li Huang; Wei Tang; Chaoqun Wang; Cong Yan; Yun Hu; Hai-Xia Yang; Hai-Yang Xiang; Xiao-Jun Huang; Li-Jun Hu; Wen-Cai Ye; Jian-Guo Song; Ying Wang (Phytochemistry, 2024)

Differential enrichment mechanism of helium in the Jinqiu gas field of Sichuan Basin, China - Kaixuan Liu; Jianfa Chen; Shuaiqi Tang; Jiaqi Zhang; Rao Fu; Cong Chen; Yi Zou; Benjian Zhang; Hua Wang; Baoshou Zhang (Marine and Petroleum Geology, 2024)

Interpretable ensemble machine learning models for predicting the shear capacity of UHPC joints - Meng Ye; Lifeng Li; Weimeng Jin; Jiahao Tang; Doo-Yeol Yoo; Cong Zhou (Engineering Structures, 2024)

Improving thermoelectric properties in double half-Heusler M8FexNi8−xSb8 (M = TiZrHfNb)-InSb compounds via synergistic multiscale defects and high-mobility carrier injection - Chaoyue Wang; Daoyong Cong; Guodong Tang; Xianglin Zhou; Jinghao Li (Chemical Engineering Journal, 2024)

Ononin inhibits triple-negative breast cancer lung metastasis by targeting the EGFR-mediated PI3K/Akt/mTOR pathway - Kumar Ganesan; Cong Xu; Jianming Wu; Bing Du; Qingqing Liu; Yue Sui; Cailu Song; Jinhui Zhang; Hailin Tang; Jianping Chen (Science China Life Sciences, 2024)

Analysis of Fracture Network Formation Mechanisms and Main Controlling Factors of Methane Explosion Fracturing in Deep Shale Reservoir - Yu Wang; Cheng Zhai; Ting Liu; Xu Yu; Jizhao Xu; Yong Sun; Yuzhou Cong; Wei Tang; Yangfeng Zheng; Ning Luo (Rock Mechanics and Rock Engineering, 2024)

ε-Polylysine treatment maintains sensory quality, texture, flavor, and inhibits aerobic bacteria growth in vacuum-packed fresh-cut lettuce - Liu Qianqian; Zhang Xin; Han Cong; Chen Qingmin; Sun Fei; Fu Maorun; Zhao Handong; Xiao Zhijian; Tang Zheng (Postharvest Biology and Technology, 2024)

Roles of quorum-sensing molecules in methane production from anaerobic digestion aided by biochar - Ai-Hua Li; Bao-Cai Zhang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Yong-Xiang Ren; Zhihua Li; Aijie Wang; Wenzong Liu (Journal of Environmental Management, 2024)

An ionic liquid-modified PEDOT/Ti3C2TX based molecularly imprinted electrochemical sensor for pico-molar sensitive detection of L-Tryptophan in milk - Cong Xue; Ruxangul Jamal; Tursun Abdiryim; Xiong Liu; Fangfei Liu; Feng Xu; Qian Cheng; Xinsheng Tang; Nana Fan (Food Chemistry, 2024)

Reprogramming protein stability in Escherichia coli to improve four-carbon dicarboxylic acids production - Jingyu Pan; Yongsheng Tang; Jia Liu; Cong Gao; Wei Song; Jing Wu; Liming Liu; Xiulai Chen (Chemical Engineering Journal, 2024)

Size-switchable and dual-targeting nanomedicine for cancer chemoimmunotherapy by potentiating deep tumor penetration and antitumor immunity - Lu Tang; Yue Yin; Ziyao Zhang; Cong Fu; Yuqi Cao; Hening Liu; Jingwen Feng; Jifan Gao; Jing Shang; Wei Wang (Chemical Engineering Journal, 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

Genome-wide analysis of polyphenol oxidase gene family in Solanum tuberosum and functional identification of StuPPO9 in regulating tolerance to Phytophthora infestans - Ming Chi; Da Tang; Cong Xue; Jieping Huang; Bo Liu; Mengqi Cao (Physiological and Molecular Plant Pathology, 2024)

Green supply chain for steel raw materials under price and demand uncertainty - Cong Cheng; HongMei Chu; Liang Zhang; LianJie Tang (Journal of Cleaner Production, 2024)

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Effects of hypo-osmotic stress on osmoregulation, antioxidant response, and energy metabolism in sea cucumber Holothuria moebii under desalination environment - Junyang Jiang; Yanna Tang; Zhaozhao Cao; Cong Zhou; Zonghe Yu (Environmental Research, 2024)

Subalpine peatland development since the Last Glacial Maximum in subtropical China: Predominantly controlled by monsoonal climate and local topography - Cong Chen; Kangyou Huang; Dehao Xie; Meiling Man; Yongjie Tang; Yuanfu Yue; Xiao Zhang; Zhuo Zheng; Rachid Cheddadi (CATENA, 2024)

A polyfunctionalized carbon framework composite for efficient decontamination of Cr(VI) and polycyclic aromatic nitrides from acidic wastewater - Weilong Wu; Han Zhang; Rong Qian; Kunru Yu; Ronghua Li; Kuok Ho Daniel Tang; Xuan Wu; Zhiqiang Guo; Cong Shao; Feixue Yue; Zengqiang Zhang (Environmental Science and Pollution Research, 2024)

Overcoming research challenges: In vitro cultivation of Ameson portunus (Phylum Microsporidia) - Ming Fu; Hongnan Qu; Yongliang Wang; Jingyu Guan; Tian Xia; Kai Zheng; Liyuan Tang; Chunxue Zhou; Huaiyu Zhou; Wei Cong; Jinyong Zhang; Bing Han (Journal of Invertebrate Pathology, 2024)

Exploring the effect of different precursor materials on Fe-loaded biochar catalysts for toluene removal - Jinzheng Wang; Chao Ye; Haofeng Yang; Hui Jin; Xinjia Wang; Jiankai Zhang; Cong Dong; Guoneng Li; Yuanjun Tang; Xingping Fang (Journal of Environmental Chemical Engineering, 2024)

Biochar derived from alkali-treated sludge residue regulates anaerobic digestion: Enhancement performance and potential mechanisms - Wen Hu; Hong-Yu Jin; Xiang-Yu Gao; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Zhang-Wei He (Environmental Research, 2024)

A big data analytics method for the evaluation of maritime traffic safety using automatic identification system data - Quandang Ma; Huan Tang; Cong Liu; Mingyang Zhang; Dingze Zhang; Zhao Liu; Liye Zhang (Ocean & Coastal Management, 2024)

Mechanism study of toluene removal using iron/nickel bimetallic catalysts supported on biochar - Haofeng Yang; Chao Ye; Jinzheng Wang; Hui Jin; Jiankai Zhang; Xinjia Wang; Cong Dong; Guoneng Li; Yuanjun Tang; Guanqun Luo; Haolin Liu; Xingping Fang; et al. (Science of The Total Environment, 2024)

Final suture of the Palaeo-Asian Ocean domain: Insights from the geochemistry and geochronology of the early to Middle Permian Elitu Formation volcanics - Jianzhou Tang; Shaohua Zhang; Zhicheng Zhang; Jinzhuang Xue; Cong Ding (Lithos, 2024)

Transition from a hydrologically partitioned to an integrated lake in the Cretaceous Junggar Basin, Central Asia - Xutong Guan; Chaodong Wu; Joel Saylor; Weiwei Jia; Xueying Tang; Yizhe Wang; Cong Lin (Journal of Asian Earth Sciences, 2024)

New perspective for Calpain-Mediated regulation of meat Quality: Unveiling the impact on mitochondrial pathway apoptosis in post-mortem - Yunhao Ma; Ying Wang; Zhaoming Wang; Yong Xie; Cheng Tang; Cong Li; Feiran Xu; Hui Zhou; Baocai Xu (Food Chemistry, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Surface engineered carbon felt toward highly reversible Fe anode for all-iron flow batteries - Yuanfang Song; Hui Yan; Zhongxiao Cong; Jing Yang; Ying Li; Ao Tang (Chemical Engineering Journal, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Bonding performance of reinforced and oil shale residue concrete - Cong Zeng; Yunyi Wang; Dehong Wang; Mingyi Tang; Mengqiu Gao; Wenqi E (Journal of Cleaner Production, 2024)

Metagenomics and untargeted metabolomics analyses to unravel the formation mechanism of characteristic metabolites in Cantonese soy sauce during different fermentation stages - Linfeng Wen; Jianping Lei; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Cong Chen; Liping He; Jiangyan Fu; Chi-Tang Ho; Qingrong Huang; Yong Cao. (Food Research International, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Inertial and kinematic demands of isolated pile-supported wharves in liquefiable soils: Centrifuge tests - Liang Tang; Zheng Zhang; Xianzhang Ling; Shengyi Cong; Pan Si (Soil Dynamics and Earthquake Engineering, 2024)

Highly dispersed amorphous nano-selenium functionalized carbon nanofiber aerogels for high-efficient uptake and immobilization of Hg(II) ions - Dongmin Zhao; Zhuoyan Li; Kaini Zhu; Ai Lu; Ying Wang; Jingjing Jiang; Cong Tang; Xing-Can Shen; Changping Ruan (Journal of Hazardous Materials, 2024)

Dynamic surface-enhanced Raman spectroscopy and positively charged probes for rapid detection and accurate identification of fungal spores in infected apples via deep learning methods - Jinghong Wang; Rui Zhu; Yehang Wu; Le Tang; Cong Wang; Mengqing Qiu; Ling Zheng; Pan Li; Shizhuang Weng (Food Control, 2024)

Mn-CaCO3-based nanosystem for augmented sonodynamic-chemodynamic immunotherapy via PI3K/Akt signaling pathway - Mashiti Sha; Huansong Li; Yangsui Liu; Cong Tang; Xue Bai; Yun Wang; Bo Yuan; Kairui Liu; Xiaoning Gao; Jun Yan; Silong Wei; Jin Chang; et al. (Chemical Engineering Journal, 2024)

Identification of the domestication gene GmCYP82C4 underlying the major quantitative trait locus for the seed weight in soybean - Yang Li; Wenqian Zhao; Jiajun Tang; Xiuli Yue; Jinbao Gu; Biyao Zhao; Cong Li; Yanhang Chen; Jianbo Yuan; Yan Lin; Yan Li; Fanjiang Kong; et al. (Theoretical and Applied Genetics, 2024)

Settlement prediction of immersed tunnel considering time-dependent foundation modulus - Shu-Yu He; Cong Tang; Wan-Huan Zhou (Tunnelling and Underground Space Technology, 2024)

Dimerized sesquiterpenoid [4 + 2] adducts with ferroptosis-promoting activity from Inula britannica Linn - Cong Guo; Hui-Jun Geng; Wen-Ji Wang; Yan-Xiang Liu; Lu Deng; Jun-Mian Tian; Jin-Ming Gao; Jiang-Jiang Tang (Phytochemistry, 2024)

Hysteretic nonlinear SMA-TMD for wind-wave-induced vibration mitigation of monopile offshore wind turbines considering stiffness degradation - Shuo Yao; Cong Liu; Xin Chen; Baijian Tang; Yong Sun; Zhiqiang Zhang (Ocean Engineering, 2024)

Research on fatigue damage mitigation of offshore wind turbines by a bi-directional PSTMD under stochastic wind-wave actions - Zhenbo Lei; Gang Liu; Yu Cong; Wei Tang (Engineering Structures, 2024)

Achieving high-rate and long-life Zn metal anodes via constructing interfacial gradient heterostructure - Yilun Ren; Biao Wang; Shaozhong Chang; Hao Wu; Yujie Ma; Fengqi Li; Cong Wang; Jian Gu; Yurong Yang; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2024)

Readily available, biocompatible sodium citrate catalyst for efficient glycerol carbonate production through transesterification of glycerol and ethylene carbonate - Haoru Tang; Cong Luo; Houfang Lu; Kejing Wu; Yingying Liu; Yingming Zhu; Binshen Wang; Bin Liang (Chemical Engineering Journal, 2024)

Revealing the roles of biochar derived from iron-rich fermented sludge residue in anaerobic digestion - Hong-Yu Jin; Zhang-Wei He; Yong-Xiang Ren; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Distribution characteristics of soil organic carbon fractions in paddy profiles with 40 years of fertilization under two groundwater levels - Kaizhao Tang; Cong Wu; Shuai Wang; Wenjuan Liao; Lichu Yin; Weijun Zhou; Hao-Jie Cui (Journal of Soils and Sediments, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Efficient Bayesian model updating for settlement prediction of the immersed tunnel of HZMB - Shu-Yu He; Sin-Chi Kuok; Cong Tang; Wan-Huan Zhou (Transportation Geotechnics, 2024)

Mass-immigration shapes the antibiotic resistome of wastewater treatment plants - Lanping Zhang; Bob Adyari; Liyuan Hou; Xiaoyong Yang; Mahmoud Gad; Yuwen Wang; Cong Ma; Qian Sun; Qiang Tang; Yifeng Zhang; Chang-Ping Yu; Anyi Hu (Science of The Total Environment, 2024)

Vertical biome shifts and climate changes since the last glacial maximum in the southeastern margin of the Tibetan plateau, Southwest China - Xiao Zhang; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Qiuchi Wan; Cong Chen; Yongjie Tang; Yuanfu Yue; Xin Jia; Zhuo Zheng (Quaternary Science Reviews, 2024)

Aluminum chloride enhances the production of short-chain fatty acids from waste activated sludge: Insights to performance, mechanism, and implications - Fei Wang; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Journal of Water Process Engineering, 2024)

Biomethane production enhancement from waste activated sludge with recycled magnetic biochar: Insights into the recycled strategies and mechanisms - Hong-Yu Jin; Yong-Xiang Ren; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang; Zhang-Wei He (Journal of Cleaner Production, 2024)

Biochar regulates anaerobic digestion: Insights to the roles of pore size - Zhang-Wei He; Ai-Hua Li; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2024)

Interfacial bidirectional binding for improving photovoltaic performance of perovskite solar cells - Mengmeng Chen; Ke Tian; Hairui Liu; Yang Liu; Ying Tang; Shan Cong; Zhenhuang Su; Feng Yang; Zhuxia Zhang; Songhua Chen; Chaochao Qin; Jien Yang; et al. (Chemical Engineering Journal, 2024)

High-precision modeling of tide-induced 3-D magnetic field and analysis of geomagnetic satellite orbit requirements - Zhengyong Ren; Cong Yang; Hongbo Yao; Xu Tang; Jingtian Tang; Keke Zhang (Science China Earth Sciences, 2024)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Mechanism of low-voltage electrostatic fields on the water-holding capacity in frozen beef steak: Insights from myofilament lattice arrays - Yong Xie; Kai Zhou; Bo Chen; Yunhao Ma; Cheng Tang; Peijun Li; Zhaoming Wang; Feiran Xu; Cong Li; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Seismic response and failure modes analysis of pile foundations in liquefiable soils using various design criteria - Xiaofeng Man; Liang Tang; Xijun Jia; Shengyi Cong; Xianzhang Ling (Soil Dynamics and Earthquake Engineering, 2023)

Fagus diversification in China in relation to East Asian monsoon evolution - Qiuchi Wan; Kangyou Huang; Su-Fang Chen; Frédéric Boyer; Pierre Taberlet; Hongwei Li; Cong Chen; Yongjie Tang; Zhuo Zheng; Xiao Zhang; Rachid Cheddadi; Qiang Fan (Quaternary Science Reviews, 2023)

Contribution identification of hydrolyzed products of potassium ferrate on promoting short-chain fatty acids production from waste activated sludge - Cong-Cong Tang; Min Zhang; Bo Wang; Zheng-Shuo Zou; Xing-Ye Yao; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Aijie Wang; Zhang-Wei He (Journal of Environmental Management, 2023)

Natural zeolite enhances anaerobic digestion of waste activated sludge: Insights into the performance and the role of biofilm - Cong-Cong Tang; Bao-Cai Zhang; Xing-Ye Yao; Thangavel Sangeetha; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang; Zhang-Wei He (Journal of Environmental Management, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Construction of an ultra-stable mixed conductive layer to stabilize the solid-state electrolyte/Na interface by in-situ interface chemistry - Yujie Yang; Yisu Hao; Yan Zhang; Cong Huang; Bin Yao; Yang Qian; Ge Chang; Zhixiao Liu; Qunli Tang; Aiping Hu; Xiaohua Chen (Chemical Engineering Journal, 2023)

A tumor microenvironment responsive titanium-based nanosonosensitizer for combination sonodynamic-immunotherapy with calcium ion overload - Cong Tang; Huansong Li; Mashiti Sha; Jianyin Song; Xue Bai; Kairui Liu; Yangsui Liu; Bo Yuan; Jun Yan; Jin Chang; Jun Kang (Chemical Engineering Journal, 2023)

Holocene millennial-scale megaflood events point to ENSO-driven extreme climate changes - Cong Chen; Yanwei Zheng; Zhuo Zheng; Yongqiang Zong; Kangyou Huang; Barry V. Rolett; Huanhuan Peng; Xiao Zhang; Yongjie Tang; Qiuchi Wan; Guifang Zhang; Rachid Chedaddi (Science China Earth Sciences, 2023)

Distinct characteristics of the bacterial community in the rhizosphere soils of sweet potato storage roots and fibrous roots following long-term fertilization - Wang Jing; Wang Lei; Yuan Jie; Xu Cong; Zhang Hui; Zhu Meng; Zhao Peng; Zhu Xiaoya; Tang Zhonghou; Wang Jidong; Zhang Yongchun (Applied Soil Ecology, 2023)

Drought-induced resource use efficiency responses in an alpine meadow ecosystem of northern Tibet - Tao Zhang; Yuanyuan Tang; Baoxin Shan; Mingjie Xu; Nan Cong; Ning Chen; Ximeng Ji; Guang Zhao; Zhoutao Zheng; Juntao Zhu; Yangjian Zhang (Agricultural and Forest Meteorology, 2023)

Holocene Evolution of the Pearl River Delta: Mapping Integral Isobaths and Delta Progradation - Yongjie Tang; Zhuo Zheng; Kangyou Huang; Cong Chen; Zhen Chen; Hongyu Lu; Weisheng Wu; Xiaoming Lin; Xianhe Zhang; Hongwei Li (Journal of Marine Science and Engineering, 2023)
The Pearl River Delta (PRD, China) has undergone complex geological development within a multi-island faulted basin, shaped by the interplay of regional tectonic movements, Quaternary sea-level fluctuations, and fluvial-marine interactions. Despite a great number of studies on the Holocene sedimentary sequences and spatial differences of lithofacies and environments, scant attention has been paid to the overarching human influence on deltaic evolution and coastline modifications since the Neolithic epoch. To further elucidate the spatial variation in Holocene sedimentation and its underlying basement topography shaped during the Last Glacial Maximum (LGM), we compiled a comprehensive dataset incorporating borehole data from over 2800 cores (the maximum depth can reach 92.5 m) within the PRD. Subsequently, high-resolution isobath maps of Quaternary deltaic deposits were generated, offering unprecedented insights into sediment distribution. This dataset facilitated a nuanced reconstruction of pre-Holocene topography, revealing a zone characterized by elongated, deep-incised valleys governed by NW-SE fault orientations. Further, we delineated coastline shifts since the period of maximum Holocene transgression (~7000 years BP), contributing to an enhanced understanding of the formation and evolutionary patterns of the delta and river network oscillations. Our findings illuminate an increasing anthropogenic impact on the rate of fluvial sedimentation and land growth, particularly accentuated over the last two millennia, favoring deltaic accretion.

Insights into the roles and mechanisms of a green-prepared magnetic biochar in anaerobic digestion of waste activated sludge - Hong-Yu Jin; Lei Yang; Yong-Xiang Ren; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Zhihua Li; Aijie Wang; Zhang-Wei He (Science of The Total Environment, 2023)

Wheat adaptation to environmental stresses under climate change: Molecular basis and genetic improvement - Hude Mao; Cong Jiang; Chunlei Tang; Xiaojun Nie; Linying Du; Yuling Liu; Peng Cheng; Yunfeng Wu; Huiquan Liu; Zhensheng Kang; Xiaojie Wang (Molecular Plant, 2023)

Revealing methane production potential from waste activated sludge through citric acid-assisted hydrogen corrosion of zero valent iron - Fei Wang; Zheng-Shuo Zou; Zhang-Wei He; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2023)

Carbon-coating small-molecule organic bipolar electrodes for symmetric Li-dual-ion batteries - Chenbin Tang; Bangshuai Wei; Wu Tang; Yan Hong; Meichen Guo; Xuesong He; Jiahui Hu; Shan Jia; Cong Fan (Chemical Engineering Journal, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Insights into response mechanism of anaerobic digestion of waste activated sludge to particle sizes of zeolite - Cong-Cong Tang; Bao-Cai Zhang; Xing-Ye Yao; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang; Zhang-Wei He (Bioresource Technology, 2023)

A major QTL simultaneously increases the number of spikelets per spike and thousand-kernel weight in a wheat line - Conghao Zhao; Jieguang Zhou; Cong Li; Jianing You; Yanling Liu; Huaping Tang; Mei Deng; Qiang Xu; Yazhou Zhang; Qiantao Jiang; Guoyue Chen; Pengfei Qi; et al. (Theoretical and Applied Genetics, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Contrasting magmatic controls on the genesis of Fe-Ti-V oxide deposits in the Emeishan large igneous province using apatite Sr-Nd isotopes and apatite-zircon trace elements - Qingyan Tang; Chusi Li; Cong Liu; Shengchao Xue; Shihai Xu; Yan Zhang; Zhuoming Li; Jian Bao; Hong Song (Mineralium Deposita, 2023)
We use Sr-Nd isotopes of apatite and trace element compositions of apatite-zircon pairs from a major ore layer in each of three selected magmatic Fe-Ti-V oxide ore deposits (Hongge, Panzhihua, and Taihe) in the Emeishan large igneous province (LIP) in southwestern China to contrast the magmatic controls on ore formation. The average contents of REEs in apatite from a representative ore zone/layer in each of these deposits are higher than the predicted values of apatite crystallizing from a melt with REE contents assumed to be the same as the average values of high-Ti basalts in the Emeishan LIP, confirming that the ore-forming magmas all experienced higher degrees of fractional crystallization by major silicate minerals than the average basalt. The apatites Sm/Yb and Sr/Y indicate that the Panzhihua magma was generated at a shallower depth and experienced higher degree of plagioclase fractional crystallization than Taihe and Hongge. The apatite Sr-Nd isotopes can be reproduced by ~ 8 wt% contamination with Precambrian gneiss-schist in the parental magma for Hongge and by ~ 10 wt% and ~ 25 wt% contamination with marbles in the parental magmas for Panzhihua and Taihe, respectively. A recycled, high-T altered oceanic gabbroic component in the mantle source is a viable alternative to the marble contamination model for Taihe. Coexisting zircon trace element compositions reveal that the parental magma for Taihe (ΔFMQ+4.0) is more oxidized than those for Hongge (ΔFMQ−0.4) and Panzhihua (ΔFMQ−0.7), questioning that magma oxidation played a critical role in the genesis of Fe-Ti-V oxide ore deposits in the Emeishan LIP.

A catastrophic rainfall-induced high landslide, occurred on December 4, 2020, in the Qingliucun mountainous area of Southwest China - Demin Xue; Cong Dai; Yingfeng Wu; Kai Chen; Jibing Tang; Shuai Zhang (Landslides, 2023)

Analysis of the optimal photosynthetic environment for an alpine meadow ecosystem - Tao Zhang; Danfeng Wang; Mingjie Xu; Nan Cong; Guang Zhao; Yuanyuan Tang; Zhoutao Zheng; Ning Chen; Juntao Zhu; Yangjian Zhang; Yongtao He (Agricultural and Forest Meteorology, 2023)

High reusability and adsorption capacity of acid washed calcium alginate/chitosan composite hydrogel spheres in the removal of norfloxacin - Jia Tang; Liangjie Wang; Weiwei Qin; Zhuolin Qing; Cong Du; Shuhu Xiao; Bingfei Yan (Chemosphere, 2023)

A catastrophic high-speed train crash caused by a small-scale debris flow in China - Shuai Zhang; Cong Dai; Shuairong Wang; Bijiao Wang; Yiling Zhou; Yanbo Chen; Bate Bate; Liangtong Zhan; Yunmin Chen; Yao Tang (Transportation Geotechnics, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Savanna/rainforest dynamics and hydroclimate changes in northern boundary of tropical Asia over the past 150 kyrs - Cong Chen; Kangyou Huang; Zhuo Zheng; Yongqiang Zong; Peter Kershaw; Shixiong Yang; Liping Tian; Meiling Man; Sheng-Hua Li; Chris Brodie; Ning Wang; Xiao Zhang; et al. (Global and Planetary Change, 2023)

Soil moisture dominates the interannual variability in alpine ecosystem productivity by regulating maximum photosynthetic capacity across the Qinghai-Tibetan Plateau - Tao Zhang; Yuanyuan Tang; Mingjie Xu; Guang Zhao; Nan Cong; Zhoutao Zheng; Juntao Zhu; Ben Niu; Zhi Chen; Yangjian Zhang; Ning Chen; Yongtao He; et al. (Global and Planetary Change, 2023)

Unveiling the complementary mechanism in the one-pot synthesis of glycerol carbonate from CO2 and glycerol - Cong Luo; Houfang Lu; Haoru Tang; Kejing Wu; Yingying Liu; Yingming Zhu; Siyang Tang; Binshen Wang; Bin Liang (Fuel, 2023)

Mechanism behind the deterioration in gel properties of collagen gel induced by high-temperature treatments: A molecular perspective - Cheng Tang; Yujuan Xu; Kai Zhou; Yong Xie; Yunhao Ma; Cong Li; Feiran Xu; Hui Zhou; Baocai Xu (Food Research International, 2023)

Transcriptome analysis reveals important regulatory genes and pathways for tuber color variation in Pinellia ternata (Thunb.) Breit - Cong Yin; Ding Tang; Xiaoyu Liu; Zihan Li; Yulin Xiang; Kaiming Gao; Heyu Li; Lin Yuan; Bisheng Huang; Juan Li (Protoplasma, 2023)

Network pharmacology and molecular docking to explore the potential mechanism of urolithin A in combined allergic rhinitis and asthma syndrome - Shuang Cong; Yan Feng; Huaping Tang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

An environmental crisis and its cultural impact in eastern China around 6000 years ago - Kangyou Huang; Dehao Xie; Cong Chen; Yongjie Tang; Qiuchi Wan; Xiao Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

LRBmat: A novel gut microbial interaction and individual heterogeneity inference method for colorectal cancer - Shan Tang; Shanjun Mao; Yangyang Chen; Falong Tan; Lihua Duan; Cong Pian; Xiangxiang Zeng (Journal of Theoretical Biology, 2023)

Mechanism of textural properties changes of cooked chicken in early postmortem: Effect of protein degradation induced by calpain on heating shrinkage - Yunhao Ma; Ying Wang; Zhaoming Wang; Bo Chen; Yong Xie; Cheng Tang; Cong Li; Kai Zhou; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Developmental and cardiac toxicity assessment of Ethyl 3-(N-butylacetamido) propanoate (EBAAP) in zebrafish embryos - Qiang Luo; Liping Ai; Shuqiong Tang; Hua Zhang; Jinze Ma; Xiaoping Xiao; Keyuan Zhong; Guiyou Tian; Bo Cheng; Cong Xiong; Xiaobei Chen; Huiqiang Lu (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Pore Structure and Damage Evaluation of Hot Dry Rocks in Enhanced Geothermal System by Combining Electrical Resistivity, Ultrasonic Waves and Nuclear Magnetic Resonance - Yong Sun; Cheng Zhai; Xu Yu; Jizhao Xu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Experimental study on impact response of seaborne rocket launch platform - Fuzhen Pang; Yuxuan Qin; Yang Tang; Cong Gao; Haichao Li (Ocean Engineering, 2023)

Utilization of constructed wetland technology in China's sponge city scheme under carbon neutral vision - Yamei Cai; Yaqian Zhao; Ting Wei; Wei Fu; Cheng Tang; Yujie Yuan; Qi Yin; Cong Wang (Journal of Water Process Engineering, 2023)

Enrichment strategies of heavy metals in the O/H/O process composed of biological fluidized bed for wastewater treatment: A case study of Cu and Zn - Cong Wei; Xiaoqian Cheng; Wei Sun; Xia Tang; Tuo Wei; Zijun Pang; Xiong Ke; Zhi Qin; Jiamin Pan; Gengrui Wei; Guanglei Qiu; Chunhua Feng; et al. (Journal of Cleaner Production, 2023)

Activation of cellulose with CO2 and/or H2O: Evolution of functionalities of the biochar and environmental impacts - Cong Ming; Yuchen Jiang; Chao Li; Qifeng Chen; Shu Zhang; Shuang Wang; Bin Li; Zhenhua Cui; Yonggui Tang; Xun Hu (Biomass and Bioenergy, 2023)

Orally administered BZL-sRNA-20 oligonucleotide targeting TLR4 effectively ameliorates acute lung injury in mice - Dandan Zhao; Yuhao Qin; Jiaqi Liu; Kegong Tang; Shuaiyao Lu; Zirui Liu; Yexuan Lin; Cong Zhang; Fengming Huang; Jiahui Chang; Chang Li; Mingyao Tian; et al. (Science China Life Sciences, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Recent advances and perspectives in roles of humic acid in anaerobic digestion of waste activated sludge - Zhang-Wei He; Fei Wang; Zheng-Shuo Zou; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhihua Li; Aijie Wang (Chemical Engineering Journal, 2023)

Natural Convection of Nanofluids in Partially Filled Metal Foam Sinusoidal Cavities - Zhen Tian; Linfei Yue; Cong Qi; Maoqing Tang (Transport in Porous Media, 2023)

Microstructure Evolution of Bituminous Coal Modified by High-Pressure CO2 Foam Fracturing Fluid with Different Treatment Times - Yangfeng Zheng; Cheng Zhai; Aikun Chen; Yong Sun; Yuzhou Cong; Wei Tang; Jizhao Xu; Xu Yu; Xinyu Zhu; Yujie Li (Natural Resources Research, 2023)

Surface-enhanced Raman spectroscopy charged probes under inverted superhydrophobic platform for detection of agricultural chemicals residues in rice combined with lightweight deep learning network - Shizhuang Weng; Le Tang; Mengqing Qiu; Jinghong Wang; Yehang Wu; Rui Zhu; Cong Wang; Pan Li; Wen Sha; Dong Liang (Analytica Chimica Acta, 2023)

Dysregulation of the microbiota-brain axis during long-term exposure to polystyrene nanoplastics in rats and the protective role of dihydrocaffeic acid - Wenbo Jiang; Cong Hu; Yunyan Chen; Yue Li; Xinyi Sun; Huanyu Wu; Ruiming Yang; Yiwei Tang; Fengru Niu; Wei Wei; Changhao Sun; Tianshu Han (Science of The Total Environment, 2023)

Holocene warming and evergreen/deciduous forest replacement across eastern China - Zhuo Zheng; Cong Chen; Kangyou Huang; Xiao Zhang; Peter Kershaw; Jun Cheng; Jie Li; Yuanfu Yue; Qiuchi Wan; Yaze Zhang; Yongjie Tang; Mengyuan Wang; et al. (Quaternary Science Reviews, 2023)

Cold blobs in the subpolar North Atlantic: seasonality, spatial pattern, and driving mechanisms - Jian Shi; Jiaqi Wang; Zixuan Ren; Cong Tang; Fei Huang (Ocean Dynamics, 2023)

Quantification of Asian monsoon variability from 68 ka BP through pollen-based climate reconstruction - Xiao Zhang; Zhuo Zheng; Kangyou Huang; Jun Cheng; Rachid Cheddadi; Yan Zhao; Chen Liang; Xiaoqiang Yang; Qiuchi Wan; Yongjie Tang; Cong Chen; Jie Li (Science Bulletin, 2023)

Dephosphorylation of CatC at Ser-18 improves salt and oxidative tolerance via promoting its tetramerization in rice - Yan Wang; Yuting Yi; Cong Liu; Heping Zheng; Jian Huang; Ye Tian; Huihui Zhang; Qiang Gao; Dongying Tang; Jianzhong Lin; Xuanming Liu (Plant Science, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

On the extinction depth of freezing-induced groundwater migration - Xiao-Wei Jiang; Hong-Yu Xie; Shemin Ge; Han Tang; Shu-Cong Tan; Xu-Sheng Wang; Li Wan; Yijian Zeng (Journal of Hydrology, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

Vitamin D receptor (VDR) mediates the quiescence of activated hepatic stellate cells (aHSCs) by regulating M2 macrophage exosomal smooth muscle cell-associated protein 5 (SMAP-5) - Xuwentai Liu; Yue Wu; Yanyi Li; Kaiming Li; Siyuan Hou; Ming Ding; Jingmin Tan; Zijing Zhu; Yingqi Tang; Yuming Liu; Qianhui Sun; Cong Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Integrating oculomics with genomics reveals imaging biomarkers for preventive and personalized prediction of arterial aneurysms - Yu Huang; Cong Li; Danli Shi; Huan Wang; Xianwen Shang; Wei Wang; Xueli Zhang; Xiayin Zhang; Yijun Hu; Shulin Tang; Shunming Liu; Songyuan Luo; et al. (EPMA Journal, 2023)
Objective Arterial aneurysms are life-threatening but usually asymptomatic before requiring hospitalization. Oculomics of retinal vascular features (RVFs) extracted from retinal fundus images can reflect systemic vascular properties and therefore were hypothesized to provide valuable information on detecting the risk of aneurysms. By integrating oculomics with genomics, this study aimed to (i) identify predictive RVFs as imaging biomarkers for aneurysms and (ii) evaluate the value of these RVFs in supporting early detection of aneurysms in the context of predictive, preventive and personalized medicine (PPPM). Methods This study involved 51,597 UK Biobank participants who had retinal images available to extract oculomics of RVFs. Phenome-wide association analyses (PheWASs) were conducted to identify RVFs associated with the genetic risks of the main types of aneurysms, including abdominal aortic aneurysm (AAA), thoracic aneurysm (TAA), intracranial aneurysm (ICA) and Marfan syndrome (MFS). An aneurysm-RVF model was then developed to predict future aneurysms. The performance of the model was assessed in both derivation and validation cohorts and was compared with other models employing clinical risk factors. An RVF risk score was derived from our aneurysm-RVF model to identify patients with an increased risk of aneurysms. Results PheWAS identified a total of 32 RVFs that were significantly associated with the genetic risks of aneurysms. Of these, the number of vessels in the optic disc (‘ntreeA’) was associated with both AAA ( β = −0.36, P = 6.75e−10) and ICA ( β = −0.11, P = 5.51e−06). In addition, the mean angles between each artery branch (‘curveangle_mean_a’) were commonly associated with 4 MFS genes ( FBN1 : β = −0.10, P = 1.63e−12; COL16A1 : β = −0.07, P = 3.14e−09; LOC105373592 : β = −0.06, P = 1.89e−05; C8orf81/LOC441376 : β = 0.07, P = 1.02e−05). The developed aneurysm-RVF model showed good discrimination ability in predicting the risks of aneurysms. In the derivation cohort, the C -index of the aneurysm-RVF model was 0.809 [95% CI: 0.780–0.838], which was similar to the clinical risk model (0.806 [0.778–0.834]) but higher than the baseline model (0.739 [0.733–0.746]). Similar performance was observed in the validation cohort, with a C -index of 0.798 (0.727–0.869) for the aneurysm-RVF model, 0.795 (0.718–0.871) for the clinical risk model and 0.719 (0.620–0.816) for the baseline model. An aneurysm risk score was derived from the aneurysm-RVF model for each study participant. The individuals in the upper tertile of the aneurysm risk score had a significantly higher risk of aneurysm compared to those in the lower tertile (hazard ratio = 17.8 [6.5–48.8], P = 1.02e−05). Conclusion We identified a significant association between certain RVFs and the risk of aneurysms and revealed the impressive capability of using RVFs to predict the future risk of aneurysms by a PPPM approach. Our finds have great potential to support not only the predictive diagnosis of aneurysms but also a preventive and more personalized screening plan which may benefit both patients and the healthcare system. Graphical abstract

Biopolymer recovery from waste activated sludge toward self-healing mortar crack - Cong Zhang; Peng Hu; Qing Liu; Zeyu Lu; Benyi Cao; Yuxin Tang; Tianwei Hao (Science of The Total Environment, 2023)

Catalytic cracking and catalyst deactivation/regeneration characteristics of Fe-loaded biochar catalysts for tar model compound - Haolin Liu; Chao Ye; Zefu Ye; Zhujun Zhu; Qisong Wang; Yuanjun Tang; Guanqun Luo; Wenwen Guo; Cong Dong; Guoneng Li; Yousheng Xu; Qinhui Wang (Fuel, 2023)

Secular trend in water discharge transport in the Lower Mekong River-delta: Effects of multiple anthropogenic stressors, rainfall, and tropical cyclones - Runan Tang; Zhijun Dai; Xuefei Mei; Xiaoyan Zhou; Chuqi Long; Cong Mai Van (Estuarine, Coastal and Shelf Science, 2023)

Bifunctional electrolyte additive with redox mediation and capacity contribution for sulfur cathode in aqueous Zn-S batteries - Ge Chang; Jilei Liu; Yisu Hao; Cong Huang; Yujie Yang; Yang Qian; Xiaohua Chen; Qunli Tang; Aiping Hu (Chemical Engineering Journal, 2023)

Efficient removal of uranium(VI) from aqueous solution by a novel phosphate-modified biochar supporting zero-valent iron composite - Ziwei Tang; Zhongran Dai; Mi Gong; Hong Chen; Xiayu Zhou; Yating Wang; Cong Jiang; Wanying Yu; Le Li (Environmental Science and Pollution Research, 2023)

Vegetation and chemical weathering changes since the late MIS 3 in the mid-lower Yangtze River Valley: Evidence from pollen and geochemical records - Cong Chen; Yongjie Tang; Kangyou Huang; Qiuchi Wan; Xiao Zhang; Dehao Xie; Hongwei Li; Kunchun Shui; Jianhua Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Oxygen vacancy-mediated peroxydisulfate activation and singlet oxygen generation toward 2,4-dichlorophenol degradation on specific CuO1−x nanosheets - Meilan Pan; Shuang-Yin Tang-Hu; Cong Li; Jianheng Hong; Subiao Liu; Bingjun Pan (Journal of Hazardous Materials, 2023)

Design of bipolar polymer electrodes for symmetric Li-dual-ion batteries - Bangshuai Wei; Yan Hong; Wu Tang; Meichen Guo; Xuesong He; Chenbin Tang; Jiahui Hu; Cong Fan (Chemical Engineering Journal, 2023)

Preparation of polyethyleneimine-modified chitosan/Ce-UIO-66 composite hydrogel for the adsorption of methyl orange - Zhi Chen; Zhi-Bo Zhang; Jun Zeng; Zhi-Jie Zhang; Shan Ma; Cong-Ming Tang; Jun-Qiang Xu (Carbohydrate Polymers, 2023)

Dynamic properties of polycrystalline ice subjected to cyclic triaxial loading - Yanyang Yu; Enlong Liu; Bingtang Song; Yu Su; Cong Chen; Shijia Tang (Cold Regions Science and Technology, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Investigation and improvement of the Mini-Max Polynomial Approximation method for solving burnup equations - Cong Zhang; Binhang Zhang; Yanzhao Bi; Xianbao Yuan; Yonghong Zhang; Haibo Tang (Annals of Nuclear Energy, 2023)

Insight into the impacts and mechanisms of ketone stress on the antibiotic resistance in Escherichia coli - Zhenping Tang; Yu Zhang; Shasha Xiao; Yuanyuan Gao; Yi Duan; Boyang Liu; Cong Xiong; Zhengqing Yang; Yueyue Wu; Shuai Zhou (Environmental Science and Pollution Research, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Stabilization of coarse-grained saline soil using microbially enhanced calcium carbonate deposition - Shengyi Cong; Liang Tang; Bo Wang; Xianzhang Ling; Lin Geng; Wenqiang Xing (Bulletin of Engineering Geology and the Environment, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Citrinin Derivatives From Penicillium Citrinum Y34 That Inhibit α-Glucosidase and ATP-Citrate Lyase - Shanji Chen; Danmei Tian; Jihua Wei; Cong Li; Yihan Ma; Xiaoshuang Gou; Yiran Shen; Mei Chen; Sihao Zhang; Jia Li; Bin Wu; Jinshan Tang (Frontiers in Marine Science, 2022)
Two new citrinin dimers bearing a 6,6-spiroketal moiety (1 and 2) and four known analogues (3–6), together with 18 known citrinin monomers (7–24), were isolated from the culture of hydrothermal vent-associated fungus Penicillium citrinum Y34. Their structures were identified by extensive spectroscopic analyses, 13 C NMR calculation in combination with DP4+, linear correlation coefficient ( R 2 ), and mean absolute error (MAE) values analyses, and electronic circular dichroism (ECD) calculation. The α -glucosidase and ATP-citrate lyase (ACL) inhibitory activities of isolated compounds were evaluated. Compounds 1, 3, and 12 displayed moderate α -glucosidase inhibitory activities with IC 50 values of 239.8, 176.2, and 424.4 μM, respectively. Enzyme kinetics investigations of 1 and 3 suggested their non-competitive inhibition of α -glucosidase with K i values of 204.3 and 212.7 μM, respectively. Meanwhile, compound 4 showed significant ACL inhibitory potential with an IC 50 value of 17.4 μM. Furthermore, the interactions of 1, 3, and 12 with α -glucosidase and 4 with ACL were investigated by molecular docking assay. This study demonstrates that citrinins, especially for their dimers, could be potential lead compounds for the development of new agents for the treatment of metabolic diseases.

Research on the layout optimization and utilization of floor gas extraction roadway: a case study in Shoushan No.1 Coal Mine, China - Xiong Ding; Cheng Zhai; Jizhao Xu; Xu Yu; Yong Sun; Yuzhou Cong; Yangfeng Zheng; Wei Tang (Arabian Journal of Geosciences, 2022)

A review of the botany, traditional uses, phytochemistry and pharmacology of Stemonae Radix - Lixia Wang; Hongwei Wu; Cong Liu; Tong Jiang; Xiaoyun Yang; Xiaoxu Chen; Liying Tang; Zhuju Wang (Phytochemistry Reviews, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Age, origin and tectonic implications of Late Carboniferous-Early Permian felsic magmatic rocks from central Inner Mongolia, south-eastern Central Asian Orogenic Belt - Jianzhou Tang; Jian Cheng; Zhicheng Zhang; Jinzhuang Xue; Bo Liu; Tiejun Duan; Weijia Zhan; Cong Ding; Qi Wang; Huaihui Zhang; Yunxi Meng (International Geology Review, 2022)

Geographical distribution and migration routes of the medical bryophyte, Climacium dendroides , under climate warming in China - Mingyang Cong; Minfei Jian; Yueyue Xu; Luyan Tang; Jinjiang Li; Wenjing Yang; Yongmei Zhu (Plant Biosystems, 2022)

Investigation on the characteristics of gut microbiota in critically endangered blue-crowned laughingthrush (Garrulax courtoisi) - Cong Wang; Jiawei Li; Yuwei Cheng; Hongbo Tang; Yanpeng Xiong; Yongfei Wu; Luping Wang; Daoqiang Liu; Jianhua Huang (Molecular Genetics and Genomics, 2022)

Effect of Metal Foam on Natural Convective Heat Transfer of Nanofluids in a Photothermal Conversion System - Zhibo Tang; Cong Qi; Liyuan Zhang; Zhen Tian (Transport in Porous Media, 2022)

Improving succinate production by engineering oxygen-dependent dynamic pathway regulation in Escherichia coli - Cong Gao; Wenxiu Tang; Liang Guo; Guipeng Hu; Jia Liu; Liming Liu; Xiulai Chen (Systems Microbiology and Biomanufacturing, 2022)

Recycling of supra-crustal materials in the rhyolites from north Sonid Youqi: implications for the crustal evolution in the southeast Central Asian Orogenic Belt - Jian-Zhou Tang; Zhicheng Zhang; Bo Liu; Shaohua Zhang; Ke Li; Qi Wang; Cong Ding (International Journal of Earth Sciences, 2022)

The impact of Typhoon Lekima (2019) on East China: a postevent survey in Wenzhou City and Taizhou City - Cong Zhou; Peiyan Chen; Shifang Yang; Feng Zheng; Hui Yu; Jie Tang; Yi Lu; Guoming Chen; Xiaoqing Lu; Xiping Zhang; Jing Sun (Frontiers of Earth Science, 2022)

Geochronology, geochemistry and zircon Hf isotope constraints on petrogenesis and tectonic setting of Early Permian volcanic rocks from Sonid Youqi area, Solonker Zone - Jianzhou Tang; Zhicheng Zhang; Bo Liu; Qi Wang; Cong Ding (International Geology Review, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Damage and Failure of Hot Dry Rock under Cyclic Liquid Nitrogen Cold Shock Treatment: A Non-destructive Ultrasonic Test Method - Yong Sun; Cheng Zhai; Jizhao Xu; Xu Yu; Yuzhou Cong; Yangfeng Zheng; Wei Tang; Yujie Li (Natural Resources Research, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Research on the functions and values of minority village sports - Cong Zeng; Jinyong Tang; Minghuan Tang; Shijun XU (Nanotechnology for Environmental Engineering, 2021)

Influence of wet flue gas desulfurization on the pollutants monitoring in FCC flue gas - Feng Ju; Cong Wu; Hui Luan; Zhihe Tang; Helin Pan; Hui Pan; Guangli Xiu; Hao Ling (Environmental Science and Pollution Research, 2021)

Expression and functional analysis of cytoplasmic dynein during spermatogenesis in Portunus trituberculatus - Chao-Guang Wei; Dan-Li Mu; Dao-Jun Tang; Jun-Quan Zhu; Cong-Cong Hou (Cell and Tissue Research, 2021)

Geochemical characteristics of the lower Cambrian Qiongzhusi Formation in Huize area, east Yunnan: implications for paleo-ocean environment and the origin of black rock series - Yong Cheng; Weiqing Liu; Wei Wu; Yu Zhang; Guo Tang; Cong Liu; Qi Nie; Yiming Wen; Ping Lu; Chuanyu Zhang (Arabian Journal of Geosciences, 2021)

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

A new approach for calculating the apparent resistivity tensor - Cong Zhou; Jing-Tian Tang; Yuan Yuan; Zheng-Yong Ren; Yong Li (Applied Geophysics, 2021)

Face stability of the slurry shield–driven tunnel with an impermeable filter cake in saturated medium sand - Xianzhang Ling; Xiangxun Kong; Liang Tang; Wenchong Tang; Shengyi Cong; Juan Zhang; Xiangping Zhao (Arabian Journal of Geosciences, 2021)

Long-lived cold blobs in the Northeast Pacific linked with the tropical La Niña - Cong Tang; Jian Shi; Chun Li (Climate Dynamics, 2021)

Trajectory prediction based on long short-term memory network and Kalman filter using hurricanes as an example - Wanting Qin; Jun Tang; Cong Lu; Songyang Lao (Computational Geosciences, 2021)
Trajectory data can objectively reflect the moving law of moving objects. Therefore, trajectory prediction has high application value. Hurricanes often cause incalculable losses of life and property, trajectory prediction can be an effective means to mitigate damage caused by hurricanes. With the popularization and wide application of artificial intelligence technology, from the perspective of machine learning, this paper trains a trajectory prediction model through historical trajectory data based on a long short-term memory (LSTM) network. An improved LSTM (ILSTM) trajectory prediction algorithm that improves the prediction of the simple LSTM is proposed, and the Kalman filter is used to filter the prediction results of the improved LSTM algorithm, which is called LSTM-KF. Through simulation experiments of Atlantic hurricane data from 1851 to 2016, compared to other LSTM and ILSTM algorithms, it is found that the LSTM-KF trajectory prediction algorithm has the lowest prediction error and the best prediction effect.

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Fluvastatin attenuated ischemia/reperfusion-induced autophagy and apoptosis in cardiomyocytes through down-regulation HMGB1/TLR4 signaling pathway - Hua-Sheng Ding; Jun Yang; Jian Yang; Xin Guo; Yan-Hong Tang; Yan Huang; Zhen Chen; Zhi-Xing Fan; Cong-Xin Huang (Molecular Biology Reports, 2021)

Seasonal Variations in Total Lipid and Fatty Acid Composition of Haliotis discus Hannai from Three Different Production Zones - Lipin Chen; Qi Wang; Xiaohan Cong; Fanqianhui Yu; Yong Xue; Qingjuan Tang; Changhu Xue; Yanqing Liu; Zhaojie Li (Journal of Aquatic Food Product Technology, 2021)

Influence of Dose on Neutrophil-Mediated Delivery of Nanoparticles for Tumor-Targeting Therapy Strategies - Min Liu; Cong Li; NaYan; Dan Zhao; Hongxia Zhang; Jie Li; Xueying Tang; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2021)

Antimicrobial compounds from marine fungi - Cong Wang; Siyan Tang; Shugeng Cao (Phytochemistry Reviews, 2021)

Multiple‐scale negative impacts of warming on ecosystem carbon use efficiency across the Tibetan Plateau grasslands - Ning Chen; Yangjian Zhang; Juntao Zhu; Nan Cong; Guang Zhao; Jiaxing Zu; Zhipeng Wang; Ke Huang; Li Wang; Yaojie Liu; Zhoutao Zheng; Ze Tang; et al. (Global Ecology and Biogeography, 2021)
Aim Ecosystem carbon use efficiency (CUEe) is a core parameter of ecosystem process models, but its relationships with climate are still uncertain, especially for ecosystems with harsh environments. Large inconsistencies in climate impacts on the CUEe have been reported among various spatial scales. The goal of this study was to examine whether warming promotes or restricts the CUEe and whether the CUEe responds to a warming gradient in a linear or nonlinear manner. Location Tibetan Plateau. Time period 2000–2018. Major taxa studied Alpine grassland ecosystem. Methods We integrated multiple‐source data of carbon fluxes and CUEe, including warming experiments at a site scale, eddy covariance observations at a landscape scale and synthesized warming experiments and ecosystem process models at a regional scale. Next, we deployed a statistical model to examine the warming impacts on the CUEe across scales; the effects of biotic and abiotic factors on the CUEe and its components were summarized based on the results of standardized major axis tests and routines, structural equation modelling and nonlinear models. Results This study reported a suppressive warming impact on the CUEe, which followed a nonlinear curve with severe inhibition in the high‐level warming treatment. With a warming threshold of 1.5–2.0°C, CUEe response patterns transitioned from no change to a significant decrease. The restriction effects can be ascribed to the joint adverse and asymmetric effects of warming on CUEe components under multiple‐level warming. Warming‐modified relationships among CUEe components and the nonlinear effects of biotic and abiotic factors led to the nonlinear responses of CUEe to warming. Main conclusions This study revealed suppressive and nonlinear effects of warming on the CUEe, including especially dramatic CUEe decreases with high‐level warming. These findings are critical for optimizing model parameters and improving predictions of the carbon sequestration capacity of alpine grasslands.

Effects of biochar amendment on greenhouse gas emission in two paddy soils with different textures - Jieyun Liu; Husen Qiu; Cong Wang; Jianlin Shen; Wenzheng Zhang; Jiumao Cai; Hong Tang; Jinshui Wu (Paddy and Water Environment, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Time-reverse location of microseismic sources in viscoelastic orthotropic anisotropic medium based on attenuation compensation - Tang Jie; Liu Ying-Chang; Wen Lei; Li Cong (Applied Geophysics, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

Aprepitant Intravenous Emulsion Based on Ion Pairing/Phospholipid Complex for Improving Physical and Chemical Stability During Thermal Sterilization - Xinyu Zhang; Ying Wei; Zhijun Cao; Ying Xu; Cong Lu; Meiqi Zhao; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Yanjiao Wang; Xing Tang (AAPS PharmSciTech, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Flag leaf size and posture of bread wheat: genetic dissection, QTL validation and their relationships with yield-related traits - Jian Ma; Yang Tu; Jing Zhu; Wei Luo; Hang Liu; Cong Li; Shuiqin Li; Jiajun Liu; Puyang Ding; Ahsan Habib; Yang Mu; Huaping Tang; et al. (Theoretical and Applied Genetics, 2020)

Role of purines in regulation of metabolic reprogramming - Zhenwei Tang; Wenrui Ye; Haotian Chen; Xinwei Kuang; Jia Guo; Minmin Xiang; Cong Peng; Xiang Chen; Hong Liu (Purinergic Signalling, 2019)

Liver Targeting Albumin-Coated Silybin-Phospholipid Particles Prepared by Nab™ Technology for Improving Treatment Effect of Acute Liver Damage in Intravenous Administration - Cong Lu; Xin Li; Xue Liang; Xinyu Zhang; Tian Yin; Jingxin Gou; Haibing He; Yu Zhang; Xing Tang (AAPS PharmSciTech, 2019)

Parametric Study on the Free-Fall Water Entry of a Sphere by Using the RANS Method - Pengyao Yu; Cong Shen; Chunbo Zhen; Haoyun Tang; Tianlin Wang (Journal of Marine Science and Engineering, 2019)
Motivated by the application of water-entry problems in the air-drop deployment of a spherical oceanographic measuring device, the free-fall water entry of a sphere was numerically investigated by using the transient Reynolds-averaged Navier–Stokes (RANS) method. A convergence study was carried out, which accounts for the mesh density and time-step independence. The present model was validated by the comparison of non-dimensional impact force with previous experimental and numerical results. Effects of parameters, such as impact velocity, radius, and mass of the sphere on the impact force and the acceleration of the sphere, are discussed. It is found that the peak value of the non-dimensional impact force is independent of the impact velocity and the radius of the sphere, while it depends on the mass of the sphere. By fitting the relationship between the peak value of the non-dimensional impact force and the non-dimensional mass, simplified formulas for the prediction of peak values of the impact force and the acceleration were achieved, which will be useful in the design of the spherical oceanographic measuring device.

The effects of air temperature and precipitation on the net primary productivity in China during the early 21st century - Qianfeng Wang; Jingyu Zeng; Song Leng; Bingxiong Fan; Jia Tang; Cong Jiang; Yi Huang; Qing Zhang; Yanping Qu; Wulin Wang; Wei Shui (Frontiers of Earth Science, 2018)

Abundance of transcripts of functional gene reflects the inverse relationship between CH4 and N2O emissions during mid-season drainage in acidic paddy soil - Hongling Qin; Yafang Tang; Jianlin Shen; Cong Wang; Chunlan Chen; Jie Yang; Yi Liu; Xiangbi Chen; Yong Li; Haijun Hou (Biology and Fertility of Soils, 2018)

Near-source noise suppression of AMT by compressive sensing and mathematical morphology filtering - Guang Li; Xiao Xiao; Jing-Tian Tang; Jin Li; Hui-Jie Zhu; Cong Zhou; Fa-Bao Yan (Applied Geophysics, 2017)

Simulated nitrogen deposition significantly suppresses the decomposition of forest litter in a natural evergreen broad-leaved forest in the Rainy Area of Western China - Shi-xing Zhou; Cong-de Huang; Bo-han Han; Yong-xiang Xiao; Jian-dong Tang; Yuan-bin Xiang; Chao Luo (Plant and Soil, 2017)

Interleukin-18, matrix metalloproteinase-22 and -29 are independent risk factors of human coronary heart disease - Dong-Yi Jin; Cong-Lin Liu; Jun-Nan Tang; Zhao-Zhong Zhu; Xue-Xi Xuan; Xiao-Dan Zhu; Yun-Zhe Wang; Tian-Xia Zhang; De-Liang Shen; Xiao-Fang Wang; Guo-Ping Shi; Jin-Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Identification of olfactory receptor genes in the Japanese grenadier anchovy Coilia nasus - Guoli Zhu; Liangjiang Wang; Wenqiao Tang; Xiaomei Wang; Cong Wang (Genes & Genomics, 2017)

Novel hemostatic agents based on gelatin-microbial transglutaminase mix - Fang Lv; Xiaonan Cong; Wenshu Tang; Yiming Han; Yu Tang; Yongrui Liu; Liqiang Su; Mingyao Liu; Mingfei Jin; Zhengfang Yi (Science China Life Sciences, 2017)

Sex Differences in Diagnosis and Clinical Phenotypes of Chinese Children with Autism Spectrum Disorder - Shihuan Wang; Hongzhu Deng; Cong You; Kaiyun Chen; Jianying Li; Chun Tang; Chaoqun Ceng; Yuanyuan Zou; Xiaobing Zou (Neuroscience Bulletin, 2017)

The boundary conditions for simulations of a shake-table experiment on the seismic response of 3D slope - Liang Tang; Shengyi Cong; Xianzhang Ling; Nengpan Ju (Earthquake Engineering and Engineering Vibration, 2017)

Genetic mapping of QTL for the sizes of eight consecutive leaves below the tassel in maize (Zea mays L.) - Cong Yang; Dengguo Tang; Jingtao Qu; Ling Zhang; Lei Zhang; Zhengjie Chen; Jian Liu (Theoretical and Applied Genetics, 2016)

Lateral flow strip for visual detection of K-ras mutations based on allele-specific PCR - Cong Wang; Xiaomin Chen; Yuying Wu; Hao Li; Yu Wang; Xiaofu Pan; Tingting Tang; Ziying Liu; Xiaokun Li (Biotechnology Letters, 2016)

Controlled attenuation parameter for the detection of hepatic steatosis in patients with chronic hepatitis B - Jing Chen; Dongbo Wu; Menglan Wang; Enqiang Chen; Lang Bai; Cong Liu; Juan Liao; Hong Tang (Infectious Diseases, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Identification of a uniquely expanded V1R (ORA) gene family in the Japanese grenadier anchovy (Coilia nasus) - Guoli Zhu; Wenqiao Tang; Liangjiang Wang; Cong Wang; Xiaomei Wang (Marine Biology, 2016)

Identification of QTL for ear row number and two-ranked versus many-ranked ear in maize across four environments - Cong Yang; Dengguo Tang; Lei Zhang; Jian Liu; Tingzhao Rong (Euphytica, 2015)

What are the effects of aromatic plants and meteorological factors on Pseudococcus comstocki and its predators in pear orchards? - Hui Hua Wan; Bei Zhou Song; Guang Bo Tang; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2015)

China’s provincial CO2 emissions embodied in trade with implications for regional climate policy - Zhangqi Zhong; Rui Huang; Qinneng Tang; Xiaonan Cong; Zheng Wang (Frontiers of Earth Science, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Cholelithiasis and risk of pancreatic cancer: systematic review and meta-analysis of 21 observational studies - Yuanfeng Gong; Siying Li; Yunqiang Tang; Cong Mai; Mingchen Ba; Peng Jiang; Hui Tang (Cancer Causes & Control, 2014)

Origin area and migration route: Chloroplast DNA diversity in the arctic-alpine plant Koenigia islandica - Cong Long; YunJiang Min; XiuXia Zhao; ChunLei Yany; Hang Sun; HouYuan Lü; LingYu Tang; ZhongZe Zhou (Science China Earth Sciences, 2014)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Repellent and attractive effects of herbs on insects in pear orchards intercropped with aromatic plants - Guang Bo Tang; Bei Zhou Song; Ling Ling Zhao; Xu Sheng Sang; Hui Hua Wan; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)

Role of autophagy in early brain injury after subarachnoid hemorrhage in rats - Hongbo Zhao; Zhiyong Ji; Deji Tang; Cong Yan; Wenyang Zhao; Cheng Gao (Molecular Biology Reports, 2013)

Isolation and characterization of 16 polymorphic microsatellite markers for the mudskipper (Boleophthalmus pectinirostris) - Cong-Tao Wang; Zhi-Zhi Liu; Ling-Bo Ma; Jia-Mei Zhang; Zhen Zeng; An-Yuan He; Shou-Jie Tang; Wen-Qiao Tang (Conservation Genetics Resources, 2012)

Cross-talk between NMDA and GABAA receptors in cultured neurons of the rat inferior colliculus - DanNi Cong; ZhengQuan Tang; LongZhu Li; YiNa Huang; Jun Wang; Lin Chen (Science China Life Sciences, 2011)

The mechanisms underlying ICa heterogeneity across murine left ventricle - Lin Xu; Xu-Yong Li; Yu Liu; Hai-Tao Li; Jing Chen; Xiao-Yan Li; Xue-Jun Jiang; Gang Wu; Yan-Hong Tang; Xi Wang; Cong-Xin Huang (Molecular and Cellular Biochemistry, 2011)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Slope runoff study in situ using rainfall simulator in mountainous area of North China - Jingjie Yu; Cong Yang; Changming Liu; Xianfang Song; Shanshan Hu; Fadong Li; Changyuan Tang (Journal of Geographical Sciences, 2009)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

Identification and Experimental Verification of Protective Antigens Against Streptococcus suis Serotype 2 Based on Genome Sequence Analysis - Lina Liu; Gong Cheng; Changjun Wang; Xiuzhen Pan; Yanguang Cong; Qu Pan; Jing Wang; Feng Zheng; Fuquan Hu; Jiaqi Tang (Current Microbiology, 2009)

Dehydration of clastic sediments in subduction zones: Theoretical study using thermodynamic data of minerals - Ying Li; Hans‐Joachim Massonne; Arne Willner; Hong‐Feng Tang; Cong‐Qiang Liu (Island Arc, 2008)
Pseudosections for two sediments and one basalt calculated in the system K 2 O–Na 2 O–CaO–MgO–FeO–Fe 2 O 3 –Al 2 O 3 –TiO 2 –SiO 2 –H 2 O for the P–T range 10 to 35 kbar, 300 to 900°C give useful insights into the amount of H 2 O released from oceanic crust in subduction zones. In cold subduction zones (20 kbar–300°C to 35 kbar–500°C) hydrous minerals storing 3 to 4 wt% H 2 O are still present in metasediments at depths of 120 km. In the same environment, metabasite releases 1 wt% H 2 O in the depth range 100 to 120 km, but 4.5 wt% H 2 O is transported to greater depths. In hot subduction zones (300°C hotter than the cold subduction zone at 100 km depth), dehydration events of metasediments in the depth range 50 to 80 km correspond to the breakdown of chlorite and paragonite. In the calculations no further water is released at greater depths because the modal content of phengite, the only hydrous mineral phase at these depths, remains almost constant. For the same P–T path, metabasite shows continuous dehydration between 40 and 80 km releasing almost 3 wt% H 2 O. At 120 km depth less than 0.4 wt% of H 2 O remains. In an average modern subduction zone (∼6°C/km) most dehydration of sediments occurs at depths of 70 to 100 km and that of basalts at depths of 80 to 120 km. Only 1.3 wt% H 2 O in metasediments and 1.6 wt% H 2 O in metabasalt has the potential to be subducted to depths greater than 120 km. The dehydration behavior of sediments concurs with the generally held idea that subduction zone fluids are most effectively transported to great depths by cold subduction. In hot subduction zones, such as those characteristic of early Earth, most H 2 O carried by oceanic crust is liberated at depths less than 120 km and, thus, would not contribute to island‐arc magmatism.

High throughput culture and gametogenesis induction of Laminaria japonica gametophyte clones - Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Shi Ju Luo; Xue Xi Tang (Journal of Applied Phycology, 2008)

Nonpoint Source Pollution Assessment of Wujiang RiverWatershed in Guizhou Province, SW China - Cong-Guo Tang; Cong-Qiang Liu (Environmental Modeling & Assessment, 2008)

Breeding of an elite Laminaria variety 90-1 through inter-specific gametophyte crossing - Quan-Sheng Zhang; Xue-Xi Tang; Yi-Zhou Cong; Shan-Cun Qu; Shi-Ju Luo; Guan-Pin Yang (Journal of Applied Phycology, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Study on construction of cDNA libraries from rat normal liver and regeneration liver with smart technique - Lin Jun-Tang; Wang Cong-Rui; Jogenananda Pramanik; Zhang Hui-Yong; Feng Hui-Gen; Yang Bao-Sheng; L. I. Yu-Chang; Xu Cun-Shuan (Indian Journal of Clinical Biochemistry, 2004)